Lead acid battery
By adding surfactant and oxygen C 2-4 composition to the negative electrode battery material of the lead-acid battery and adding specific ions to the electrolyte, the problem of accumulating bismuth sulfate and overcharge capacity of the battery in a partially charged state is solved, and higher charging acceptability and life expectancy are achieved.
Patent Information
- Application Number
- JP2022565144
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-27
- Filing Date
- 2021-10-28
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-10-28
AI Technical Summary
When existing lead-acid batteries are repeatedly charged and discharged under partial charging states, bismuth sulfate is easily accumulated, resulting in a decrease in life performance. At the same time, high charging acceptability will cause overcharge to generate overcharge during overcharging, reducing battery life.
By optimizing the electrolyte concentration and the composition of the negative electrode battery material, the charging acceptability and lifespan performance of the battery are improved by optimizing the electrolyte concentration and the composition of the negative electrode battery material.
It effectively reduces the generation of overcharged charge, improves the charging acceptability of the battery and the life performance under partial charging states, and extends the service life of the battery.
Smart Images

Figure 0007661978000005 
Figure 0007661978000001 
Figure 0007661978000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a lead-acid battery. [Background technology]
[0002] Lead-acid batteries are used in a variety of applications, including automotive and industrial use. Lead-acid batteries include negative and positive plates, separators (or mats), and electrolytes. Additives are sometimes added to the components of lead-acid batteries to impart various functions.
[0003] Patent Document 1 discloses a flooded lead-acid battery having a configuration in which a negative electrode plate formed by packing a negative electrode active material in a negative electrode current collector and a positive electrode plate formed by packing a positive electrode active material in a positive electrode current collector are stacked with a separator between them, and the plate group is housed in a battery case together with an electrolyte, and charging is performed intermittently and high-rate discharging to a load is performed in a partially charged state. Patent Document 1 discloses that at least a carbonaceous conductive material and an organic compound that suppresses coarsening of the negative electrode active material due to charging and discharging are added to the negative electrode active material, and the positive electrode plate has a unit plate pack volume [cm 3 ] Total surface area of positive electrode active material [m 2 ] to 3.5 to 15.6 [m 2 / cm 3 In addition, a compound selected from a cationic flocculant, a cationic surfactant, and phosphoric acid is added to the electrolyte.
[0004] Patent Document 2 proposes an electrolyte for a lead acid battery containing an ammonium compound represented by a specific formula (I).
[0005] Patent Document 3 proposes a lead acid battery in which a copolymer of propylene oxide and ethylene oxide is added to the negative electrode plate and the material in combination with lignin sulfonate.
[0006] Patent Document 4 proposes a rechargeable electrochemical cell that is subjected to multiple charge and discharge cycles. Each charge cycle has a charge portion corresponding to a gassing charge where gas is generated in the cell and a charge portion lower than the gassing charge. The electrochemical cell has a positive electrode and a negative electrode, an aqueous electrolyte in ionic contact with the electrodes that supports a current flow between the electrodes, and an inactivatable inhibiting means disposed in the electrolyte and a component thereof bound to the negative electrode to form a barrier that inhibits the gassing charge. The inactivatable inhibiting means is activated by a charge portion corresponding to the gassing charge such that, when activated, the inactivatable inhibiting means inhibits the gassing charge and limits gas generation in the cell, and is inactivated by a charge portion lower than the gassing charge such that, when inactivated, the inactivatable inhibiting means has substantially no effect of limiting the charge and has substantially no effect during the discharge cycle. Patent Document 4 describes a quaternary ammonium such as an alkyl dimethyl benzyl ammonium chloride as the inactivatable inhibiting means.
[0007] Patent Document 5 proposes a lead-acid battery comprising a negative electrode material containing carbon, a bisphenol-based condensate, at least one of alginic acid or a salt thereof, and sponge-like lead, a positive electrode material containing lead dioxide as a main component, and an electrolyte solution containing at least any one of aluminum ions, lithium ions, and sodium ions.
[0008] Patent Document 6 proposes a polymer nanopolymer electrolyte for lead-acid batteries, which is mainly a mixture of 2.5-4 wt% of a coordinating agent, 2.5-4 wt% of a complexing agent, 0.01-0.5 wt% of a catalyst, 2.3-3.8 wt% of a stabilizer, 0.1-0.5 wt% of a regulator, 0.01-0.5 wt% of an antifoaming agent, 36-45 wt% of sulfuric acid, and the balance of water. Here, the complexing agent is sodium carboxymethylcellulose or polyacrylamide, the stabilizer is lithium sulfate or an alkali containing lithium ions, the antifoaming agent is glycerin polyoxyethylene polyoxypropylene ether or tributyl phosphate, the regulator is sodium hydroxide or potassium hydroxide, or sodium carbonate, the coordinating agent is nano-fumed silica with a diameter of 8-15 nm, and the catalyst is sodium amide or sodium metal 99.5.
[0009] Patent Document 7 proposes a lead-acid battery having a combination of a positive electrode plate formed by filling a porous substrate made of a Pb-Ca alloy with a positive electrode active material containing calcium, and an electrolyte containing aluminum ions. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] International Publication No. 2013 / 058058 [Patent Document 2] JP 2008-152973 A [Patent Document 3] Japanese Patent Application Publication No. 182662 / 1983 [Patent Document 4] U.S. Patent No. 6,899,978 [Patent Document 5] JP 2015-32481 A [Patent Document 6] Chinese Patent No. 100439438 [Patent Document 7] JP 2006-4636 A Summary of the Invention [Problem to be solved by the invention]
[0011] Lead-acid batteries are sometimes used in a partially charged state (PSOC). For example, lead-acid batteries installed in idle stop-start (ISS) vehicles are used in PSOC. When lead-acid batteries are repeatedly charged and discharged in PSOC, lead sulfate easily accumulates and the life performance is easily reduced. In order to suppress the accumulation of lead sulfate, high charge acceptance is required. However, when the charge acceptance is high, the reduction reaction of hydrogen ions during overcharging also becomes prominent, so the overcharged amount of electricity increases and the decrease in electrolyte becomes significant. When the surface of the lead contained in the negative electrode material is covered with an organic additive, the reduction reaction of hydrogen ions during overcharging becomes difficult to occur, so the overcharged amount of electricity can be reduced. However, when the surface of the lead is covered with an organic additive, the lead sulfate generated during discharge becomes difficult to dissolve during charging, so the charge acceptance decreases. Therefore, it is difficult to suppress the decrease in charge acceptance and reduce the overcharged amount of electricity at the same time. [Means for solving the problem]
[0012] One aspect of the present invention is a lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate comprises a negative electrode material, The negative electrode material is a surfactant and oxy C 2-4 The composition includes at least one additive selected from the group consisting of a polymer compound having a repeating structure of an alkylene unit and a surfactant, and an organic shrink-proofing agent, The electrolyte contains metal ions, The metal ions include at least one component selected from the group consisting of lithium ions, sodium ions, and aluminum ions; The total concentration of the components in the electrolyte is 0.02 mol / L or more; The concentration of each of the components in the electrolyte is 0.35 mol / L or less. [Brief description of the drawings]
[0013] [Figure 1] 1 is a partially cutaway exploded perspective view showing the appearance and internal structure of a lead-acid battery according to one aspect of the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In general, in a lead-acid battery, the reaction during overcharging is greatly influenced by the reduction reaction of hydrogen ions at the interface between lead and the electrolyte. When an organic additive is contained in the negative electrode material of a lead-acid battery, the organic additive adheres to the surface of lead, which is an active material. When the surface of lead is covered with an organic additive, the reduction reaction of hydrogen ions is difficult to occur, so the overcharged quantity of electricity tends to decrease. However, the organic additive also adheres to the surface of lead sulfate generated during discharge, making it difficult for lead sulfate to dissolve during charging, and the charge acceptance decreases. Therefore, there is a trade-off between suppressing the decrease in charge acceptance and reducing the overcharged quantity of electricity, and it has been difficult to achieve both in the past. Furthermore, when the organic additive is unevenly distributed in the pores of the lead, it is necessary to increase the content of the organic additive in the negative electrode material in order to ensure a sufficient effect of reducing the overcharged quantity of electricity. However, generally, increasing the content of the organic additive reduces the charge acceptance.
[0015] In lead-acid batteries, sulfuric acid aqueous solution is generally used as the electrolyte, so if an organic additive (oil, polymer, organic shrinkage inhibitor, etc.) is contained in the negative electrode material, it becomes difficult to balance the elution into the electrolyte and the adsorption to lead. For example, if an organic additive with low adsorption to lead is used, it becomes easy to elute into the electrolyte, making it difficult to reduce the amount of overcharge electricity. On the other hand, if an organic additive with high adsorption to lead is used, it becomes difficult to adhere thinly to the lead surface, and the organic additive tends to be unevenly distributed in the pores of the lead.
[0016] When organic additives are unevenly distributed within the pores of the lead, the steric hindrance of the unevenly distributed organic additives inhibits the movement of ions (such as lead ions and sulfate ions). This makes it easier for charge and discharge reactions to be inhibited. If the content of the organic additives is increased in order to ensure a sufficient effect of reducing the amount of overcharge electricity, the movement of ions within the pores is further inhibited, further inhibiting the charge and discharge reactions. If the charge and discharge reactions are inhibited, the charge acceptance and discharge performance will decrease.
[0017] In view of the above, a lead-acid battery according to one aspect of the present invention includes at least one cell including an electrode plate group and an electrolyte. The electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate. The negative electrode plate includes a negative electrode material. The negative electrode material includes a surfactant and oxy-C. 2-4 The electrolyte contains at least one additive (hereinafter referred to as the first additive) selected from the group consisting of polymer compounds having a repeating structure of alkylene units, and an organic shrink-proofing agent. The electrolyte contains metal ions. The metal ions contain at least one component (hereinafter referred to as the first component) selected from the group consisting of lithium ions, sodium ions, and aluminum ions. The total concentration of the first component in the electrolyte is 0.02 mol / L or more. The concentration of each of the first components in the electrolyte is 0.35 mol / L or less.
[0018] According to a lead-acid battery according to one aspect of the present invention, by combining a negative electrode plate including a negative electrode material containing an organic shrinkage inhibitor and a first additive with an electrolyte containing the first component at the above-mentioned concentration, it is possible to reduce the amount of electricity in overcharge while ensuring high charge acceptance. By suppressing hydrogen generation during overcharge, it is possible to reduce the amount of electrolyte loss. In addition, it is also possible to significantly improve the life performance when charging and discharging are repeated in a PSOC cycle (hereinafter referred to as PSOC life performance).
[0019] In the lead-acid battery according to one aspect of the present invention, the overcharged amount of electricity can be reduced while ensuring a relatively high charge acceptance due to the following reasons.
[0020] First, the first additive is Oxy C 2-4 The repeating structure of alkylene units or the presence of hydrophilic groups in the surfactant provide high adsorption to lead. In addition, in a lead-acid battery, hydrogen sulfate ions are adsorbed on the lead surface in the negative electrode material, but the anionic nature of the hydrogen sulfate ions is alleviated by the action of the first component. This effect is considered to be more pronounced when the first additive has a hydrophobic group. Therefore, it is considered that the adsorption of the first additive to the lead surface is further increased. In addition, when the first additive is oxy-C 2-4 When the surfactant has a repeating structure of alkylene units, it is easy to have a linear structure. In addition, the surfactant can suppress excessive coating on the lead surface due to the action of the hydrophobic group, and since it is amphiphilic, it is thought that aggregation is unlikely to occur. Therefore, a wide area of the lead surface is thinly and widely covered with the first additive. As a result, the hydrogen overvoltage increases, and the side reaction of generating hydrogen during overcharging is unlikely to occur, so the overcharged amount of electricity can be reduced. Even if the negative electrode material contains a very small amount of the first additive, the effect of reducing the overcharged amount of electricity can be obtained, so by including the first additive in the negative electrode material, it can be present in the vicinity of lead, and it is thought that this will cause the first additive to exhibit a high adsorption effect on lead.
[0021] The effect of reducing the amount of overcharge electricity is exhibited by covering the surface of lead in the negative electrode material with the first additive. Therefore, it is important that the first additive is present in the vicinity of lead in the negative electrode material, and this allows the effect of the first additive to be effectively exhibited. Therefore, it is important that the negative electrode material contains the first additive, regardless of whether the first additive is contained in components of the lead-acid battery other than the negative electrode material.
[0022] When the negative electrode material contains an organic additive, the organic additive adheres not only to the lead surface but also to the surface of lead sulfate generated during discharge, so that the solubility of lead sulfate during charging tends to decrease. However, since the thickness of the coating of the first additive covering the surface of lead and lead sulfate is thin, the degree to which the coating of the first additive inhibits the dissolution of lead sulfate and the transfer of electrons when lead ions are reduced to lead during charging is reduced. In addition, since the coating of the first additive is thin and uneven distribution is suppressed, the steric hindrance caused by the coating of the first additive is reduced, so that the inhibition of the movement of lead ions in the pores of the negative electrode material is reduced. Therefore, a high diffusion rate of lead ions is maintained. As a result, even when the negative electrode material contains the first additive and an organic shrinkage inhibitor, which are organic additives, the inhibition of the charge and discharge reaction can be reduced. In addition, since the electrolyte contains the first component at a specific content, the crystal growth of lead sulfate in the negative plate during discharge is difficult to proceed, so that the coarsening of lead sulfate is suppressed. Furthermore, it is believed that the presence of the first component in the electrolyte solution in the vicinity of lead sulfate reduces the adsorption of the first additive to the surface of lead sulfate. As a result, the coating of the first additive on the lead sulfate is further reduced. In this way, it is believed that a high diffusion rate of lead ions can be ensured, coarsening of lead sulfate can be suppressed, and excessive coating of the first additive on the lead sulfate can be suppressed, thereby ensuring high charge acceptance.
[0023] In this way, in the lead acid battery according to one aspect of the present invention, the coarsening of lead sulfate is suppressed and high charge acceptance is obtained. As a result, even when charge and discharge are repeated in a PSOC cycle, accumulation of lead sulfate is reduced and the progress of sulfation, which inactivates accumulated lead sulfate, can be suppressed. Therefore, high PSOC life performance can be ensured.
[0024] On the other hand, even if the electrolyte contains the first component at a specific concentration, if the negative electrode material contains an organic shrinkage inhibitor and does not contain the first additive, it is possible to ensure a certain degree of high charge acceptance and PSOC life performance. However, the effect of reducing the overcharge charge is not obtained. Also, even if the negative electrode material contains an organic shrinkage inhibitor and the first additive, if the electrolyte does not contain the first component, it is possible to reduce the overcharge charge to a certain degree, but the charge acceptance decreases and the PSOC life performance is almost unchanged or decreases. In response to these results, in a lead-acid battery according to one aspect of the present invention, by combining a negative electrode plate including a negative electrode material containing an organic shrinkage inhibitor and the first additive with an electrolyte containing the first component at a specific concentration, as described above, it is possible to greatly improve the charge acceptance while reducing the overcharge charge. Also, it is possible to greatly improve the PSOC life performance. Each of these effects is better than expected when an electrolyte solution containing a specific concentration of the first component is combined with a negative plate having a negative electrode material containing an organic shrinkage preventer and not containing the first additive, and when a negative electrode material containing an organic shrinkage preventer and the first additive is combined with an electrolyte solution not containing the first component. In other words, in the lead-acid battery according to one aspect of the present invention, by combining a negative plate having a negative electrode material containing an organic shrinkage preventer and the first additive with an electrolyte solution containing the first component at a specific concentration, a synergistic effect is obtained in reducing the overcharge electricity quantity and improving the charge acceptance and PSOC life performance.
[0025] When the total concentration of the first components in the electrolyte is less than 0.02 mol / L, it is difficult to ensure high charge acceptance. In addition, by setting the concentration of each of the first components in the electrolyte to 0.35 mol / L or less, high charge acceptance can be ensured and the overcharge charge amount can be reduced. In addition, excellent PSOC life performance can be ensured. The concentration of each of the first components in the electrolyte is preferably 0.25 mol / L or less. In this case, the first components are easily prevented from being converted into sulfates and growing into crystals together with lead sulfate. Therefore, the charge acceptance can be further suppressed and the PSOC life performance can be further suppressed. In addition, when a large amount of the first components is attracted to the electric double layer formed on the lead surface, the adsorption of the first additive to the lead surface itself tends to be inhibited. However, by controlling the concentration of each of the first components in the electrolyte as described above, the overcharge charge amount to the lead surface can be kept low.
[0026] The first component preferably contains at least one of lithium ions and sodium ions, and aluminum ions. In this case, the charge acceptance and PSOC life performance can be further improved. In addition, the overcharged amount of electricity can be further reduced.
[0027] From the viewpoint of ensuring higher charge acceptance, the first component preferably contains at least lithium ions and aluminum ions.
[0028] The first additive preferably contains a compound having a repeating structure of an oxypropylene unit (-O-CH(-CH3)-CH2-). In addition, such a compound may not contain a repeating structure of an oxyethylene unit (-O-CH2-CH2-). In these cases, the charge acceptance and PSOC life performance are further improved, and the overcharge charge is further reduced. Since a compound containing a repeating structure of an oxypropylene unit is likely to form a linear structure, it is considered that the overcharge charge is reduced by thinly and widely covering the lead surface. In addition, the repeating structure of an oxypropylene unit is more hydrophobic than the repeating structure of an oxyethylene unit. Therefore, when a compound containing a repeating structure of an oxypropylene unit is used, it is considered that the adsorption to lead sulfate is lower than when a compound containing a repeating structure of an oxyethylene unit is used, and a higher charge acceptance can be ensured.
[0029] The compound having a repeating structure of oxypropylene units preferably has a number average molecular weight (Mn) of 1000 or more and 10000 or less. In this case, the first additive is likely to remain in the negative electrode material, and the overcharged electricity quantity can be further reduced. In addition, the effect of suppressing uneven distribution of the first additive on the lead surface is enhanced, and thus the charge acceptance and PSOC life performance can be further improved.
[0030] When the first additive contains sulfur element, the first additive tends to be easily adsorbed to the surface of lead sulfate due to the action of the first component present in the vicinity of lead sulfate. Therefore, it is preferable that the first additive does not contain sulfur element. This reduces the adsorption of the first additive to lead sulfate, making it easier to ensure higher charge acceptance and PSOC life performance.
[0031] The surfactant preferably includes a cationic surfactant. The cationic surfactant preferably includes a quaternary ammonium salt type cationic surfactant. Since the cationic surfactant has a cationic hydrophilic group, in the absence of the first component, the cationic surfactant exhibits high adsorption to the lead surface due to the action of hydrogen sulfate ions present in the vicinity of lead and lead sulfate, and is likely to be attached to the surface of lead sulfate generated during discharge. When the electrolyte contains the first component at the above-mentioned concentration, the adsorption of the cationic surfactant to the lead surface is alleviated by the action of the first component, making it easier to cover a wide area of the lead surface thinly and widely. In addition, the cationic surfactant is electrically repelled by the first component present in the vicinity of lead sulfate, and the adsorption of the cationic surfactant to lead sulfate is further reduced. Therefore, it is possible to obtain higher charge acceptance and PSOC life performance while keeping the overcharge electricity quantity low.
[0032] Cationic surfactants are generally classified into amine salt type, quaternary ammonium salt type, etc. The cationic surfactant preferably contains a quaternary ammonium salt (in other words, a cationic surfactant of quaternary ammonium salt type). When a quaternary ammonium salt is used, not only can high charge acceptance and PSOC life performance be obtained, but also the highly cationic hydrophilic group exhibits higher adsorption to the lead surface than amine salts, so that the amount of overcharge electricity can be further reduced.
[0033] The negative electrode material may include a carbonaceous material. The first additive may have at least one hydrophobic group and one hydrophilic group. At least one of the hydrophobic groups may be a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms. The action of the long-chain aliphatic hydrocarbon group having 8 or more carbon atoms reduces the adsorption of the first additive to the lead surface, reducing excessive coating. In addition, the first additive is easily adsorbed to the carbonaceous material, reducing uneven distribution of the first additive on the lead sulfate surface. Therefore, it is easy to ensure higher charge acceptance and PSOC life performance while keeping the overcharge electricity quantity low.
[0034] Since the first additive is an organic additive, if it is contained in the negative electrode material, the charge acceptance is usually reduced. However, in the lead-acid battery according to one aspect of the present invention, the first additive and the first component directly or indirectly interact with each other to thinly cover the lead surface, while the coverage of the lead sulfate surface can be reduced. Therefore, the overcharge quantity of electricity can be reduced, and high charge acceptance and PSOC life performance can be ensured. Such an effect can be obtained even if the content of the first additive in the negative electrode material is small. From the viewpoint of ensuring a higher effect of reducing the overcharge quantity of electricity, the content of the first additive in the negative electrode material is preferably 50 ppm or more by mass. From the viewpoint of easily ensuring higher charge acceptance and PSOC life performance, the content of the first additive in the negative electrode material is preferably 10,000 ppm or less by mass.
[0035] In the lead-acid battery, the origin of the first additive contained in the negative electrode material is not particularly limited as long as the first additive can be contained in the negative electrode material. The first additive may be contained in any of the components of the lead-acid battery (e.g., the negative electrode plate, the positive electrode plate, the electrolyte, and the separator) when the lead-acid battery is produced. The first additive may be contained in one component, or in two or more components (e.g., the negative electrode plate and the electrolyte).
[0036] The organic shrinkage inhibitor preferably contains a condensate of a bisarene compound. The bisarene compound is generally classified as a synthetic organic shrinkage inhibitor. In general, when the negative electrode material contains a condensate of a bisarene compound, the specific surface area of the negative electrode material increases, so that the overcharged amount of electricity tends to increase. However, in the lead-acid battery according to one aspect of the present invention, since an electrolyte containing a first component at a specific concentration is combined with a negative electrode plate including a negative electrode material containing an organic shrinkage inhibitor and a first additive, even when the organic shrinkage inhibitor contains a condensate of a bisarene compound, the overcharged amount of electricity can be kept low. By using the condensate of a bisarene compound, the uneven distribution of the organic shrinkage inhibitor is reduced compared to a lignin compound, so that higher charge acceptance and PSOC life performance are easily obtained.
[0037] The lead acid battery may be either a valve regulated (sealed) lead acid battery (VRLA type lead acid battery) or a flooded (vented) lead acid battery.
[0038] In this specification, the content of the first additive in the negative electrode material and the concentration of the first component in the electrolyte are determined for a negative electrode plate and an electrolyte taken out from a fully charged lead-acid battery, respectively.
[0039] (Terminology explanation) (electrode material) The negative electrode material and the positive electrode material are usually held by a current collector. The electrode material is the portion of the electrode plate excluding the current collector. A member such as a mat or pasting paper may be attached to the electrode plate. Such a member (also called an attachment member) is included in the electrode plate because it is used integrally with the electrode plate. When the electrode plate includes an attachment member (such as a mat or pasting paper), the electrode material is the portion of the electrode plate excluding the current collector and the attachment member.
[0040] Among the positive plate, the clad type positive plate includes a plurality of porous tubes, a core metal (spine) inserted into each tube, a current collector connecting the plurality of core metals (spine), a positive electrode material filled in the tube into which the core metal (spine) is inserted, and a linking seat (spine protector) connecting the plurality of tubes. In the clad type positive plate, the positive electrode material is the portion of the plate excluding the tube, the core metal (spine), the current collector, and the linking seat (spine protector). In the clad type positive plate, the core metal (spine) and the current collector are sometimes collectively referred to as the positive electrode current collector.
[0041] (Polymer Compound) Among the first additives, the oxy-C contained in the polymer compound 2-4 The alkylene unit is -OR 1 -(R 1 is C 2-4 The polymer compound is a unit represented by oxy C 2-4As long as the polymer has a repeating structure of alkylene units, Mn is not particularly limited. For example, the number average molecular weight (Mn) of the polymer compound may be 300 or more.
[0042] (Organic shrink-proofing agent) The organic shrinkage inhibitor is an organic compound that inhibits the shrinkage of lead, which is the negative electrode active material, when a lead-acid battery is repeatedly charged and discharged. Organic shrinkage inhibitors often contain sulfur element.
[0043] (Sulfur content in organic shrinkage inhibitors) The content of sulfur element in an organic shrink-preventer being X μmol / g means that the content of sulfur element contained in 1 g of the organic shrink-preventer is X μmol.
[0044] (Condensation product of bisarene compound) The condensation product of bisarene compound is a condensation product containing a unit of bisarene compound. The unit of bisarene compound means a unit derived from bisarene compound incorporated in the condensation product. The bisarene compound is a compound in which two parts each having an aromatic ring are linked via a single bond or a linking group.
[0045] (number average molecular weight) In the present specification, the number average molecular weight (Mn) is determined by gel permeation chromatography (GPC). The standard substance used in determining Mn is polyethylene glycol.
[0046] (Weight average molecular weight) In this specification, the weight average molecular weight (Mw) is determined by GPC. The standard substance used in determining Mw is sodium polystyrene sulfonate.
[0047] (Concentration of the first component in the electrolyte) The concentration of each of the first components in the electrolyte solution means the concentration of each of the lithium ions, sodium ions, and aluminum ions. The total concentration of the first component in the electrolyte is the sum of the concentrations of the individual ions. For example, when the electrolyte contains lithium ions, sodium ions, and aluminum ions, the sum of the concentrations of these ions is the total concentration of the first component.
[0048] (fully charged) The fully charged state of a flooded lead-acid battery is defined by JIS D 5301:2019. More specifically, the fully charged state is defined as a state in which the lead-acid battery is charged in a water tank at 25°C ± 2°C with a current (A) that is 0.2 times the value (unit: Ah) listed as the rated capacity until the terminal voltage (V) during charging measured every 15 minutes or the electrolyte density converted to a temperature of 20°C shows a constant value with three significant digits three consecutive times. In addition, in the case of a valve-regulated lead-acid battery, the fully charged state is defined as a state in which constant-current constant-voltage charging of 2.23 V / cell is performed in an air tank at 25°C ± 2°C with a current (A) that is 0.2 times the value (unit: Ah) listed as the rated capacity, and charging is terminated when the charging current during constant-voltage charging becomes 0.005 times the value (unit: Ah) listed as the rated capacity.
[0049] A fully charged lead-acid battery refers to a lead-acid battery that has already been chemically prepared and is fully charged. A lead-acid battery may be fully charged immediately after chemical preparation, or after a certain amount of time has passed since chemical preparation (for example, a lead-acid battery that is in use (preferably in the early stages of use) after chemical preparation may be fully charged). An early stage battery refers to a battery that has not been in use for very long and has hardly deteriorated at all.
[0050] (Top and bottom directions of lead-acid batteries or components of lead-acid batteries) In this specification, the up-down direction of a lead-acid battery or components of the lead-acid battery (such as plates, a battery case, and a separator) refers to the up-down direction in the vertical direction of the lead-acid battery when the lead-acid battery is in use. Each of the positive and negative plates has a lug for connecting to an external terminal. In some cases, such as a horizontal valve-regulated lead-acid battery, the lug is provided on the side of the plate so as to protrude laterally, but in most lead-acid batteries, the lug is usually provided on the top of the plate so as to protrude upward.
[0051] Hereinafter, the lead-acid battery according to the embodiment of the present invention will be described in detail with respect to each of its main components, but the present invention is not limited to the following embodiment.
[0052] [Lead acid battery] (Negative plate) The negative electrode plate usually includes a negative electrode current collector in addition to a negative electrode material.
[0053] (Negative electrode current collector) The negative electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the negative electrode current collector because it is easy to support the negative electrode material.
[0054] The lead alloy used for the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element. The negative electrode current collector may have a surface layer. The surface layer and the inner layer of the negative electrode current collector may have different compositions. The surface layer may be formed on a part of the negative electrode current collector. The surface layer may be formed on the ear of the negative electrode current collector. The surface layer of the ear may contain Sn or an Sn alloy.
[0055] (Negative electrode material) The negative electrode material includes a first additive and an organic shrinkage inhibitor. The negative electrode material further includes a negative electrode active material (specifically, lead or lead sulfate) that exhibits capacity through an oxidation-reduction reaction. The negative electrode material may include at least one selected from the group consisting of a carbonaceous material and an additive other than the first additive. The additive other than the first additive may be referred to as a second additive. Examples of the second additive include, but are not limited to, barium sulfate and fibers (such as resin fibers). Note that the negative electrode active material in a charged state is sponge-like lead, but an unformed negative plate is usually made using lead powder.
[0056] (First additive) The first additive is Oxy C 2-4 At least one selected from the group consisting of polymer compounds having a repeating structure of alkylene units and surfactants. 2-4 Polymer compounds having a repeating structure of alkylene units also include polymer compounds classified as surfactants (more specifically, nonionic surfactants).
[0057] (Polymer Compound) Polymer compounds containing oxy-C 2-4 Examples of the alkylene unit include an oxyethylene unit, an oxypropylene unit, an oxytrimethylene unit, an oxy2-methyl-1,3-propylene unit, an oxy1,4-butylene unit, and an oxy1,3-butylene unit. 2-4 The alkylene unit may have one type or two or more types.
[0058] Such polymer compounds are measured using deuterated chloroform as a solvent. 1 In the chemical shift of the H-NMR spectrum, oxyC is in the range of 3.2 ppm to 3.8 ppm. 2-4 The peaks derived from alkylene units are shown.
[0059] In polymer compounds, oxyC 2-4The repeating structure of the alkylene unit is a kind of oxy C 2-4 may contain an alkylene unit, 2-4 The polymer compound may contain one type of the repeating structure or two or more types of the repeating structures.
[0060] Examples of the polymer compound include oxy C 2-4 Poly(C) is a hydroxy compound with repeating alkylene units. 2-4 Alkylene glycol, oxy C 2-4 Polyol polyC, a copolymer containing repeating alkylene units 2-4 alkylene oxide adducts, and ethers or esters of these hydroxy compounds.
[0061] As copolymers, different oxy C 2-4 Copolymers containing alkylene units, etc. The copolymer may be a block copolymer.
[0062] The polyol may be any of aliphatic polyols, alicyclic polyols, aromatic polyols, and heterocyclic polyols. From the viewpoint of facilitating thin spreading of the polymer compound on the lead surface, aliphatic polyols and alicyclic polyols (e.g., polyhydroxycyclohexane, polyhydroxynorbornane) are preferred, and among them, aliphatic polyols are preferred. Examples of aliphatic polyols include aliphatic diols and polyols having a triol or more (e.g., glycerin, trimethylolpropane, pentaerythritol, sugar, or sugar alcohol). Examples of aliphatic diols include alkylene glycols having 5 or more carbon atoms. Examples of alkylene glycols include C 5~14 Alkylene glycol or C 5-10The sugar or sugar alcohol may be, for example, sucrose, erythritol, xylitol, mannitol, or sorbitol. The sugar or sugar alcohol may be either a chain structure or a cyclic structure. In the polyalkylene oxide adduct of the polyol, the alkylene oxide is an oxy-C of the polymer compound. 2-4 Corresponding to an alkylene unit, at least C 2-4 In view of the ease with which the polymer compound has a linear structure, the polyol is preferably a diol.
[0063] The etherified product is the above-mentioned oxy C 2-4 At least some of the terminal -OH groups (composed of a hydrogen atom of the terminal group and an oxygen atom bonded to the hydrogen atom) of the hydroxy compound having a repeating structure of alkylene units are etherified to form -OR 2 Groups, where R 2 is an organic group.) Some or all of the terminals of the polymer compound may be etherified. For example, one terminal of the main chain of a linear polymer compound is an -OH group and the other terminal is an -OR group. 2 It may also be a group.
[0064] The esterified product is the above-mentioned oxy C 2-4 At least some of the terminal -OH groups (composed of a hydrogen atom of the terminal group and an oxygen atom bonded to this hydrogen atom) of a hydroxy compound having a repeating structure of an alkylene unit are esterified to form -OC(=O)-R 3 Groups, where R 3 is an organic group.) Some or all of the terminals of the polymer compound may be esterified. For example, one terminal of the main chain of a linear polymer compound is an -OH group and the other terminal is an -OC(=O)-R 3 It may also be a group.
[0065] organic group R 2 and R 3Each of the above may be a hydrocarbon group. The hydrocarbon group may have a substituent (e.g., a hydroxy group, an alkoxy group, and / or a carboxy group). The hydrocarbon group may be any of aliphatic, alicyclic, and aromatic. The aromatic hydrocarbon group and the alicyclic hydrocarbon group may have an aliphatic hydrocarbon group (e.g., an alkyl group, an alkenyl group, an alkynyl group) as a substituent. The number of carbon atoms in the aliphatic hydrocarbon group as a substituent may be, for example, 1 to 30, 1 to 20, 1 to 10, 1 to 6, or 1 to 4.
[0066] Examples of the aromatic hydrocarbon group include aromatic hydrocarbon groups having 24 or less carbon atoms (e.g., 6 to 24). The number of carbon atoms in the aromatic hydrocarbon group may be 20 or less (e.g., 6 to 20), 14 or less (e.g., 6 to 14), or 12 or less (e.g., 6 to 12). Examples of the aromatic hydrocarbon group include aryl groups and bisaryl groups. Examples of the aryl group include phenyl groups and naphthyl groups. Examples of the bisaryl group include monovalent groups corresponding to bisarenes. Examples of the bisarenes include biphenyl, bisarylalkanes (e.g., bisC 6-10 Aryl C 1-4 Alkanes (such as 2,2-bisphenylpropane) are examples.
[0067] Examples of the alicyclic hydrocarbon group include alicyclic hydrocarbon groups having 16 or less carbon atoms. The alicyclic hydrocarbon group may be a cross-linked cyclic hydrocarbon group. The number of carbon atoms in the alicyclic hydrocarbon group may be 10 or less or 8 or less. The number of carbon atoms in the alicyclic hydrocarbon group may be, for example, 5 or more, or 6 or more.
[0068] The alicyclic hydrocarbon group may have 5 (or 6) or more and 16 (or less), 5 (or 6) or more and 10 (or less), or 5 (or 6) or more and 8 (or less) carbon atoms.
[0069] Examples of alicyclic hydrocarbon groups include cycloalkyl groups (cyclopentyl, cyclohexyl, cyclooctyl, etc.) and cycloalkenyl groups (cyclohexenyl, cyclooctenyl, etc.). Alicyclic hydrocarbon groups also include hydrogenated products of the above aromatic hydrocarbon groups.
[0070] From the viewpoint of facilitating thin adhesion of the polymer compound to the lead surface, among the hydrocarbon groups, an aliphatic hydrocarbon group is preferred. The aliphatic hydrocarbon group may be saturated or unsaturated. Examples of the aliphatic hydrocarbon group include an alkyl group, an alkenyl group, an alkynyl group, a dienyl group having two carbon-carbon double bonds, and a trienyl group having three carbon-carbon double bonds. The aliphatic hydrocarbon group may be either linear or branched.
[0071] The number of carbon atoms in the aliphatic hydrocarbon group is, for example, 30 or less, and may be 26 or less or 22 or less, 20 or less or 16 or less, 14 or less or 10 or less, or 8 or less or 6 or less. The lower limit of the number of carbon atoms depends on the type of the aliphatic hydrocarbon group, and is 1 or more for alkyl groups, 2 or more for alkenyl groups and alkynyl groups, 3 or more for dienyl groups, and 4 or more for trienyl groups. Among these, alkyl groups and alkenyl groups are preferred from the viewpoint of facilitating thin adhesion of the polymer compound to the lead surface.
[0072] Specific examples of alkyl groups include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, i-pentyl, s-pentyl, 3-pentyl, t-pentyl, n-hexyl, 2-ethylhexyl, n-octyl, n-nonyl, n-decyl, i-decyl, undecyl, lauryl (dodecyl), tridecyl, myristyl, pentadecyl, cetyl, heptadecyl, stearyl, icosyl, henicosyl, and behenyl.
[0073] Specific examples of the alkenyl group include vinyl, 1-propenyl, allyl, cis-9-heptadecen-1-yl, palmitoleyl, and oleyl. 2-30 Alkenyl group or C 2-26 may be an alkenyl group, C 2-22 Alkenyl group or C 2-20 may be an alkenyl group, C 10-20 It may be an alkenyl group.
[0074] Among the polymer compounds, oxy C 2-4 Ethers of hydroxy compounds with repeating alkylene units and oxy C 2-4 It is preferable to use at least one selected from the group consisting of esters of hydroxy compounds having a repeating structure of an alkylene unit, since this can further enhance the effect of suppressing the decrease in charge acceptance. In addition, the amount of electricity during overcharging can be reduced even when these polymer compounds are used. Among these polymer compounds, a polymer compound having a repeating structure of an oxypropylene unit or a polymer compound having a repeating structure of an oxyethylene unit is preferable.
[0075] The polymer compound may have one or more hydrophobic groups. Examples of the hydrophobic group include, among the above-mentioned hydrocarbon groups, aromatic hydrocarbon groups, alicyclic hydrocarbon groups, and long-chain aliphatic hydrocarbon groups. Examples of the long-chain aliphatic hydrocarbon group include, among the above-mentioned aliphatic hydrocarbon groups (alkyl groups, alkenyl groups, etc.), aliphatic hydrocarbon groups having 8 or more carbon atoms. The number of carbon atoms in the aliphatic hydrocarbon group is preferably 12 or more, more preferably 16 or more. Among them, a polymer compound having a long-chain aliphatic hydrocarbon group is preferable because it is less likely to cause excessive adsorption to lead and further enhances the effect of suppressing the decrease in charge acceptance. The polymer compound may be a polymer compound in which at least one of the hydrophobic groups is a long-chain aliphatic hydrocarbon group. The number of carbon atoms in the long-chain aliphatic hydrocarbon group may be 30 or less, 26 or less, or 22 or less.
[0076] The carbon number of the long-chain aliphatic hydrocarbon group may be 8 or more (or 12 or more) and 30 or less, 8 or more (or 12 or more) and 26 or less, 8 or more (or 12 or more) and 22 or less, 10 or more and 30 or less (or 26 or less), or 10 or more and 22 or less.
[0077] Among the polymer compounds, those having a hydrophilic group and a hydrophobic group correspond to nonionic surfactants. The repeating structure of the polyoxyethylene unit exhibits high hydrophilicity and can be a hydrophilic group in the nonionic surfactant. Therefore, it is preferable that the polymer compound having the hydrophobic group contains a repeating structure of an oxyethylene unit. Such a polymer compound can selectively adsorb to lead while suppressing excessive coverage of the lead surface due to the balance between hydrophobicity and high hydrophilicity due to the repeating structure of the oxyethylene unit, so that the effect of suppressing the decrease in charge acceptance can be further enhanced while reducing the amount of overcharge electricity. Such a polymer compound can ensure high adsorption to lead even if it has a relatively low molecular weight (for example, Mn is 1000 or less).
[0078] Among the above polymer compounds, polyoxypropylene-polyoxyethylene block copolymers, etherified products of hydroxy compounds having a repeating structure of oxyethylene units, and esterified products of hydroxy compounds having a repeating structure of oxyethylene units correspond to nonionic surfactants.
[0079] In addition, in a polyoxypropylene-polyoxyethylene block copolymer, the repeating structure of the oxyethylene unit corresponds to a hydrophilic group, and the repeating structure of the oxypropylene unit corresponds to a hydrophobic group. Such a copolymer is also included in the polymer compound having a hydrophobic group.
[0080] Examples of polymer compounds having a hydrophobic group and containing a repeating structure of an oxyethylene unit include etherified polyethylene glycol (such as alkyl ethers), esterified polyethylene glycol (such as carboxylates), etherified polyethylene oxide adducts of the above polyols (such as alkyl ethers), and esterified polyethylene oxide adducts of the above polyols (such as triols or higher polyols). Specific examples of such polymer compounds include polyethylene glycol oleate, polyethylene glycol dioleate, polyethylene glycol dilaurate, polyethylene glycol distearate, polyoxyethylene coconut oil fatty acid sorbitan, polyoxyethylene sorbitan oleate, polyoxyethylene sorbitan stearate, polyoxyethylene lauryl ether, polyoxyethylene tetradecyl ether, and polyoxyethylene cetyl ether. However, the polymer compounds are not limited to these. Among them, the use of esterified polyethylene glycol, esterified polyethylene oxide adducts of the above polyols, and the like is preferable because it can ensure higher charge acceptance and significantly reduce the amount of overcharge electricity.
[0081] From the viewpoint of further enhancing the effect of reducing the amount of electricity in overcharging and easily ensuring higher charge acceptance and PSOC life performance, it is also preferable that the first additive contains a polymer compound containing a repeating structure of an oxypropylene unit. 1 In the chemical shift of the H-NMR spectrum, peaks due to -CH< and -CH2- of the oxypropylene unit are present in the range of 3.2 ppm to 3.8 ppm. The peaks are split due to differences in electron density around the nuclei of the hydrogen atoms in these groups. Such a polymer compound is 1In the chemical shift of the H-NMR spectrum, for example, there are peaks in the range of 3.2 ppm to 3.42 ppm and in the range of more than 3.42 ppm to 3.8 ppm. The peak in the range of 3.2 ppm to 3.42 ppm is derived from -CH2-, and the peak in the range of more than 3.42 ppm to 3.8 ppm is derived from -CH< and -CH2-.
[0082] Examples of polymer compounds containing at least a repeating structure of oxypropylene units include polypropylene glycol, copolymers containing a repeating structure of oxypropylene units, polypropylene oxide adducts of the above polyols, and etherified or esterified products thereof. Examples of copolymers include oxypropylene-oxyalkylene copolymers (wherein the oxyalkylene is a C alkylene other than oxypropylene). 2-4 Examples of the oxypropylene-oxyalkylene copolymer include oxypropylene-oxyethylene copolymer and oxypropylene-oxytrimethylene copolymer. The oxypropylene-oxyalkylene copolymer may be called polyoxypropylene-polyoxyalkylene copolymer (for example, polyoxypropylene-polyoxyethylene copolymer). The oxypropylene-oxyalkylene copolymer may be a block copolymer (for example, polyoxypropylene-polyoxyethylene block copolymer). Examples of the etherified product include polypropylene glycol alkyl ether and alkyl ether of oxypropylene-oxyalkylene copolymer (alkyl ether of polyoxypropylene-polyoxyethylene copolymer, etc.). Examples of the esterified product include polypropylene glycol ester of carboxylic acid and carboxylic acid ester of oxypropylene-oxyalkylene copolymer (carboxylic acid ester of polyoxypropylene-polyoxyethylene copolymer, etc.).
[0083] Examples of polymer compounds containing at least a repeating structure of oxypropylene units include polypropylene glycol, polyoxypropylene-polyoxyethylene copolymers (polyoxypropylene-polyoxyethylene block copolymers, etc.), polypropylene glycol alkyl ethers (see above R 2 alkyl ethers (methyl ether, ethyl ether, butyl ether, etc.) in which R is an alkyl having 10 or less carbon atoms (or 8 or less or 6 or less), polyoxyethylene-polyoxypropylene alkyl ethers (the above R 2 alkyl ethers (butyl ether, hydroxyhexyl ether, etc.) in which R is an alkyl having 10 or less carbon atoms (or 8 or less or 6 or less), polypropylene glycol carboxylates (the above R 3 Examples of the polymer compound include polypropylene glycol carboxylates (such as polypropylene glycol acetates) in which the alkyl group has 10 or less carbon atoms (or 8 or less or 6 or less), and polypropylene oxide adducts of triol or higher polyols (such as polypropylene oxide adducts of glycerin). However, the polymer compound is not limited to these.
[0084] In the polymer compound containing a repeating structure of oxypropylene units, the proportion of the oxypropylene units is, for example, 5 mol% or more, and may be 10 mol% or more, or 20 mol% or more. The proportion of the oxypropylene units is, for example, 100 mol% or less.
[0085] From the viewpoint of further improving the charge acceptance and PSOC life performance and further reducing the amount of overcharge electricity, it is also preferable that the polymer compound having a repeating structure of an oxypropylene unit does not contain a repeating structure of an oxyethylene unit. Among them, when the first additive containing at least polypropylene glycol is used, excellent effects are easily obtained.
[0086] The first additive may contain one type of polymer compound or may contain two or more types of polymer compounds.
[0087] The polymer compound may, for example, include a compound having an Mn of 5 million or less, a compound having an Mn of 1 million or less, a compound having an Mn of 100,000 or less, or a compound having an Mn of 50,000 or less or a compound having an Mn of 20,000 or less. From the viewpoint of reducing the uneven distribution of the polymer compound in the negative electrode material and ensuring higher charge acceptance and PSOC life performance, the polymer compound preferably includes a compound having an Mn of 10,000 or less, and may include a compound having an Mn of 9,000 or less or an Mn of 8,000 or less. The Mn of such a compound may be 300 or more, 400 or more, or may be 500 or more. From the viewpoint of further enhancing the effect of the polymer compound remaining in the negative electrode material and reducing the overcharge electricity amount, the Mn of such a compound is preferably 1,000 or more, more preferably 1,500 or more. As the polymer compound, two or more compounds having different Mn may be used. That is, the polymer compound may be a polymer compound having multiple Mn peaks in the molecular weight distribution. The Mn of a polymer compound having a repeating structure of an oxypropylene unit (including a polymer compound having no repeating structure of an oxyethylene unit) may be within this range.
[0088] The Mn of the above compounds is 300 or more (or 400 or more) 5 million or less, 300 or more (or 400 or more) 1 million or less, 300 or more (or 400 or more) 100,000 or less, 300 or more (or 400 or more) 50,000 or less, 300 or more (or 400 or more) 20,000 or less, 300 or more (or 400 or more) 10,000 or less, 300 or more (or 400 or more) 9,000 or less, 300 or more (or 400 or more) 8,000 or less, 500 or more (or 1,000 or more) 5 million or less, 500 or more (or 1,000 or more) 1 million or less, 500 or more (or 10 00 or more) 100,000 or less, 500 or more (or 1000 or more) 50,000 or less, 500 or more (or 1000 or more) 20,000 or less, 500 or more (or 1000 or more) 10,000 or less, 500 or more (or 1000 or more) 9,000 or less, 500 or more (or 1000 or more) 8,000 or less, 1500 or more 5,000,000 or less, 1500 or more 1,000,000 or less, 1500 or more 50,000 or less, 1500 or more 20,000 or less, 1500 or more 10,000 or less, 1500 or more 9,000 or less, or 1500 or more 8,000 or less. The Mn of a polymer compound having a repeating structure of an oxypropylene unit (including a polymer compound not having a repeating structure of an oxyethylene unit) may be in such a range.
[0089] (Surfactant) Examples of the surfactant include cationic surfactants, nonionic surfactants, anionic surfactants, and amphoteric surfactants. The surfactant contains a hydrophilic group and a hydrophobic group. The hydrophobic group of the surfactant is a functional group that is more hydrophobic than the hydrophilic group. The first additive may contain one type of surfactant or a combination of two or more types of surfactants.
[0090] A typical nonionic surfactant is a compound having a repeating structure of oxyethylene units and a hydrophobic group, and the description of the polymer compound can be referred to. As the nonionic surfactant, a fatty acid ester of a polyol (such as a polyol (such as a sugar or sugar alcohol) exemplified for the polymer compound) may be used. As the anionic surfactant, a carboxylate, a sulfonate, a sulfate ester salt, etc. may be used. As the amphoteric surfactant, an amino acid type amphoteric surfactant, a betaine type amphoteric surfactant, etc. may be used. From the viewpoint of easily securing higher charge acceptance and PSOC life performance while suppressing the overcharge electricity quantity to a low level, it is preferable that the surfactant contains a cationic surfactant. From the same viewpoint, it is also preferable to use a surfactant containing the above nonionic surfactant.
[0091] Cationic surfactants are classified into amine salt type and quaternary ammonium salt type according to the type of hydrophilic group. In the cationic surfactant, the amine salt portion or the quaternary ammonium salt portion corresponds to the hydrophilic group. In the negative electrode material, the hydrophilic group may exist in the form of a salt or in the form of a cation. The type of anion forming the salt is not particularly limited, and examples thereof include halide ions and anions derived from inorganic acids. Examples of halide ions include fluoride ions, chloride ions, bromide ions, and iodide ions. Examples of inorganic acids corresponding to anions derived from inorganic acids include hydrohalic acids (such as hydrochloric acid and hydrobromic acid) or oxo acids (such as sulfuric acid and phosphoric acid).
[0092] A cationic surfactant usually has one hydrophilic group in one molecule, but it is not intended to exclude the case where the cationic surfactant has a plurality of hydrophilic groups in one molecule.
[0093] A cationic surfactant has one or more hydrophobic groups in one molecule. Examples of the hydrophobic group include the hydrocarbon group or hydrophobic group described for the polymer compound. The number of hydrophobic groups in the cationic surfactant may be one or more, and may be two or more or three or more. An amine salt type cationic surfactant may usually have one or more and three or less hydrophobic groups per nitrogen atom of the amine salt. A quaternary ammonium salt type cationic surfactant may usually have four hydrophobic groups per nitrogen atom of the ammonium salt.
[0094] At least one of the hydrophobic groups of the cationic surfactant is preferably a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms. The long-chain aliphatic hydrocarbon group having 8 or more carbon atoms of the cationic surfactant may be referred to as a first hydrophobic group. When the cationic surfactant has a first hydrophobic group, it becomes easier to ensure higher charge acceptance and PSOC life performance while keeping the overcharge electricity quantity low. The cationic surfactant may have one or more hydrophobic groups (also referred to as a second hydrophobic group) other than the first hydrophobic group.
[0095] The cationic surfactant may have one or more first hydrophobic groups in one molecule. When the cationic surfactant has two or more first hydrophobic groups in one molecule, the types of at least two first hydrophobic groups may be the same, or all the first hydrophobic groups may be different. The upper limit of the number of first hydrophobic groups in the cationic surfactant is not particularly limited. In the amine salt type, the number of first hydrophobic groups is, for example, 3 or less, and may be 2 or less. In the quaternary ammonium salt type, the number of first hydrophobic groups is, for example, 4 or less, and may be 3 or less or 2 or less.
[0096] The number of first hydrophobic groups contained in one molecule of a cationic surfactant of an amine salt type is, for example, 1 to 3, and may be 1 to 2, or may be 2 to 3. The number of first hydrophobic groups contained in one molecule of a cationic surfactant of a quaternary ammonium salt type is, for example, 1 to 4, and may be 1 to 3 or 1 to 2, or may be 2 to 4, or 2 to 3.
[0097] The cationic surfactant may have one second hydrophobic group, or may have two or more. When the cationic surfactant has two or more second hydrophobic groups, the types of at least two second hydrophobic groups may be the same, or all the second hydrophobic groups may be different. The upper limit of the number of second hydrophobic groups is not particularly limited, and may be, for example, 2 or less in the amine salt type, and may be, for example, 3 or less or 2 or less in the quaternary ammonium salt type. In the cationic surfactant, the total number of the first hydrophobic group and the second hydrophobic group in one molecule is not more than 3 per nitrogen atom in the amine salt type, and not more than 4 in the quaternary ammonium salt type.
[0098] From the viewpoint of making it easier to reduce the thickness of the cationic surfactant coating formed on the lead surface, the first hydrophobic group is preferably an alkyl group or an alkenyl group.
[0099] The carbon number of the first hydrophobic group is, for example, 30 or less. From the viewpoint of easily ensuring high adsorption of the cationic surfactant to the lead surface by a balance with the hydrophilic group, the carbon number of the first hydrophobic group is preferably 26 or less, more preferably 24 or less or 22 or less. In addition, the negative electrode material may contain a carbonaceous material, and when the carbon number of the long-chain aliphatic hydrocarbon group is 26 or less (for example, 24 or less or 22 or less), the adsorption of the cationic surfactant to the carbonaceous material is reduced, and adsorption to the lead surface occurs easily. Therefore, the overcharge electricity quantity can be further reduced.
[0100] Examples of the second hydrophobic group include the hydrocarbon groups described for the polymer compound. The hydrocarbon group may be a hydrocarbon group having a substituent (e.g., an alkoxy group). The hydrocarbon group may be any of aliphatic, alicyclic, and aromatic. The aliphatic hydrocarbon group may have at least one selected from the group consisting of aromatic hydrocarbon groups (e.g., a phenyl group, a tolyl group, a naphthyl group) and alicyclic hydrocarbon groups (e.g., a cyclopentyl group, a cyclohexyl group) as a substituent. Examples of the aliphatic hydrocarbon group having such a substituent include a benzyl group, a phenethyl group, and a cyclohexylmethyl group. The number of carbon atoms of the aromatic hydrocarbon group and the alicyclic hydrocarbon group as the substituent may be, for example, 5 or more and 20 or less, and may be 6 or more and 12 or less. The aromatic hydrocarbon group and the alicyclic hydrocarbon group may each have an aliphatic hydrocarbon group (e.g., an alkyl group, an alkenyl group, an alkynyl group) as a substituent. The number of carbon atoms in the aliphatic hydrocarbon group as the substituent may be, for example, 1 to 30, 1 to 20, 1 to 10, 1 to 6, or 1 to 4. For other details regarding the second hydrophobic group, the explanation of the hydrocarbon group regarding the polymer compound can be referred to.
[0101] From the viewpoint of facilitating thin adhesion of the cationic surfactant to the lead surface, the second hydrophobic group is preferably an aliphatic hydrocarbon group among the hydrocarbon groups. The carbon number of the aliphatic hydrocarbon group is less than 8 and may be 6 or less. The lower limit of the carbon number is 1 or more for an alkyl group, 2 or more for an alkenyl group and an alkynyl group, 3 or more for a dienyl group, and 4 or more for a trienyl group depending on the type of the aliphatic hydrocarbon group. The second hydrophobic group is preferably an alkyl group or an alkenyl group (especially an alkyl group). The carbon number of the alkyl group is more preferably 4 or less, and may be 3 or less or 2 or less.
[0102] Specific examples of alkyl groups as the second hydrophobic group include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, i-pentyl, s-pentyl, 3-pentyl, t-pentyl, and n-hexyl.Specific examples of alkenyl groups include vinyl, 1-propenyl, and allyl.
[0103] From the viewpoint of easily obtaining high adsorption to lead due to high hydrophilicity, the cationic surfactant preferably contains at least a quaternary ammonium salt type cationic surfactant. The cationic surfactant may contain an amine salt type cationic surfactant in addition to the quaternary ammonium salt type cationic surfactant.
[0104] Examples of the quaternary ammonium salt type cationic surfactant include tetraalkylammonium salt and alkylbenzalkonium chloride. Examples of the tetraalkylammonium salt include cationic surfactants having one first hydrophobic group (octyltrimethylammonium chloride, stearyltrimethylammonium chloride, cetyltrimethylammonium chloride, behenyltrimethylammonium chloride, etc.), and cationic surfactants having two first hydrophobic groups (distearyldimethylammonium chloride, etc.). As the tetraalkylammonium salt, a cationic surfactant having four second hydrophobic groups (tetramethylammonium chloride, etc.) may be used. Examples of the alkylbenzalkonium chloride include stearylbenzyldimethylammonium chloride, stearyldimethylbenzylammonium chloride, and stearylbenzalkonium chloride. Examples of the amine salt type cationic surfactant include n-octylamine hydrochloride and dodecylamine hydrochloride. These are merely examples, and the cationic surfactant is not limited to these specific examples.
[0105] The first additive may contain one type of cationic surfactant, or may contain two or more types of cationic surfactant.
[0106] Many surfactants other than nonionic surfactants have relatively low molecular weight compounds. The Mn of the nonionic surfactant can be selected from the range of Mn described for the polymer compound. From the viewpoint of ensuring higher charge acceptance, it is preferable that the nonionic surfactant contains a compound with Mn of 10,000 or less.
[0107] Among the first additives, the anionic surfactants or amphoteric surfactants include surfactants containing a sulfur element derived from a >S=O group or the like. When the first additive contains a sulfur element, the first additive tends to be more adsorbed to lead sulfate. Therefore, it is preferable that the first additive does not contain a sulfur element. In this case, the adsorption of the first additive to lead sulfate can be reduced, making it easier to ensure higher charge acceptance and PSOC life performance.
[0108] The content of the first additive in the negative electrode material is, for example, 8 ppm or more by mass. From the viewpoint of further enhancing the effect of reducing the amount of electricity in overcharge, the content of the first additive in the negative electrode material is, for example, 10 ppm or more or 50 ppm or more by mass, more preferably 100 ppm or more, and may be 300 ppm or more or 400 ppm or more by mass. The content of the first additive in the negative electrode material is, for example, 10000 ppm or less, may be 6000 ppm or less or 5000 ppm or less, or may be 1000 ppm or less or 700 ppm or less by mass.
[0109] The content of the first additive in the negative electrode material is, by mass, 8 ppm or more (or 10 ppm or more) and 10,000 ppm or less, 8 ppm or more (or 10 ppm or more) and 6,000 ppm or less, 8 ppm or more (or 10 ppm or more) and 5,000 ppm or less, 8 ppm or more (or 10 ppm or more) and 1,000 ppm or less, 8 ppm or more (or 10 ppm or more) and 700 ppm or less, 50 ppm or more (or 100 ppm or more) and 10,000 ppm or less, 50 ppm or more (or 100 ppm or more) and 6,000 ppm or less, 50 ppm or more (or 100 ppm or more) but not more than 5000 ppm, 50 ppm or more (or 100 ppm or more) but not more than 1000 ppm, 50 ppm or more (or 100 ppm or more) but not more than 700 ppm, 300 ppm or more (or 400 ppm or more) but not more than 10,000 ppm, 300 ppm or more (or 400 ppm or more) but not more than 6,000 ppm, 300 ppm or more (or 400 ppm or more) but not more than 5,000 ppm, 300 ppm or more (or 400 ppm or more) but not more than 1000 ppm, or 300 ppm or more (or 400 ppm or more) but not more than 700 ppm.
[0110] (Organic shrink-proofing agent) Organic shrink-proofing agents are generally classified into lignin compounds and synthetic organic shrink-proofing agents. Synthetic organic shrink-proofing agents can also be said to be organic shrink-proofing agents other than lignin compounds. Examples of organic shrink-proofing agents contained in the negative electrode material include lignin compounds and synthetic organic shrink-proofing agents. The negative electrode material may contain one type of organic shrink-proofing agent or two or more types of organic shrink-proofing agents.
[0111] Examples of the lignin compound include lignin and lignin derivatives. Examples of the lignin derivatives include lignin sulfonic acid or salts thereof (alkali metal salts (sodium salts, etc.)).
[0112] The synthetic organic shrink-proofing agent is an organic polymer containing elemental sulfur, and generally contains multiple aromatic rings in the molecule and elemental sulfur as a sulfur-containing group. Among the sulfur-containing groups, sulfonic acid groups or sulfonyl groups, which are stable, are preferred. The sulfonic acid groups may exist in the acid form or in the salt form such as Na salt.
[0113] At least a lignin compound may be used as the organic shrinkage inhibitor. Lignin compounds tend to have low charge acceptance compared to synthetic organic shrinkage inhibitors. However, by including the first additive in the negative electrode material, high charge acceptance can be ensured even when a lignin compound is used as the organic shrinkage inhibitor.
[0114] As the organic shrink-proofing agent, it is also preferable to use a condensation product containing at least an aromatic compound unit. For example, such a condensation product may be a condensation product of an aromatic compound with an aldehyde compound (at least one selected from the group consisting of aldehydes (e.g., formaldehyde) and condensates thereof). The organic shrink-proofing agent may contain one type of aromatic compound unit, or may contain two or more types of aromatic compound units. The aromatic compound unit refers to a unit derived from an aromatic compound incorporated in the condensation product.
[0115] Examples of the aromatic rings that aromatic compounds have include benzene rings and naphthalene rings. When aromatic compounds have multiple aromatic rings, the multiple aromatic rings may be linked by direct bonds or linking groups (e.g., alkylene groups (including alkylidene groups), sulfone groups) and the like. Examples of such structures include bisarene structures (biphenyl, bisphenylalkane, bisphenylsulfone, etc.). Examples of aromatic compounds include compounds having the above aromatic rings and at least one selected from the group consisting of hydroxyl groups and amino groups. The hydroxyl group or amino group may be directly bonded to the aromatic ring, or may be bonded as an alkyl chain having a hydroxyl group or amino group. The hydroxyl group also includes salts of the hydroxyl group (-OMe). The amino group also includes salts of the amino group (specifically, salts with anions). Examples of Me include alkali metals (Li, K, Na, etc.) and metals of Group 2 of the periodic table (Ca, Mg, etc.).
[0116] As the aromatic compound, a bisarene compound [bisphenol compound, hydroxybiphenyl compound, bisarene compound having an amino group (bisarylalkane compound having an amino group, bisarylsulfone compound having an amino group, biphenyl compound having an amino group, etc.), hydroxyarene compound (hydroxynaphthalene compound, phenol compound, etc.), aminoarene compound (aminonaphthalene compound, aniline compound (aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, etc.)), etc.] are preferable. The aromatic compound may further have a substituent. The organic shrinkage inhibitor may contain one or more of the residues of these compounds. As the bisphenol compound, bisphenol A, bisphenol S, bisphenol F, etc. are preferable. When the negative electrode material contains a condensate of a bisarene compound (such as a condensate of an aldehyde compound), the overcharged amount of electricity tends to increase, but the overcharged amount of electricity can be kept low by the direct or indirect interaction of the first component and the first additive. In addition, the charge acceptance and PSOC life performance can be improved compared to the case of using a lignin compound.
[0117] The condensate preferably contains at least a unit of an aromatic compound having a sulfur-containing group. In particular, the use of a condensate containing at least a unit of a bisphenol compound having a sulfur-containing group is advantageous in terms of ensuring higher charge acceptance. From the viewpoint of increasing the effect of reducing the amount of overcharge electricity, it is also preferable to use a condensate of an aldehyde compound with a naphthalene compound having a sulfur-containing group and at least one selected from the group consisting of a hydroxyl group and an amino group.
[0118] The sulfur-containing group may be directly bonded to an aromatic ring contained in the compound, or may be bonded to the aromatic ring as an alkyl chain having a sulfur-containing group. The sulfur-containing group is not particularly limited, and examples thereof include a sulfonyl group, a sulfonic acid group, and salts thereof.
[0119] Also, as the organic shrink-proofing agent, for example, at least one condensate containing at least one selected from the group consisting of the above-mentioned bisarene compound units and monocyclic aromatic compound units (hydroxyarene compounds and / or aminoarene compounds, etc.) may be used. The organic shrink-proofing agent may at least contain a condensate containing a bisarene compound unit and a monocyclic aromatic compound unit (particularly, a hydroxyarene compound). Such a condensate may be a condensate of a bisarene compound and a monocyclic aromatic compound with an aldehyde compound. As the hydroxyarene compound, a phenolsulfonic acid compound (such as phenolsulfonic acid or a substituted product thereof) is preferable. As the aminoarene compound, aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, etc. are preferable. As the monocyclic aromatic compound, a hydroxyarene compound is preferable.
[0120] The negative electrode material may contain, for example, an organic shrink-proofing agent (first organic shrink-proofing agent) having a sulfur element content of 2000 μmol / g or more among the above organic shrink-proofing agents. Examples of the first organic shrink-proofing agent include the above synthetic organic shrink-proofing agents (such as the above condensates).
[0121] The sulfur element content of the first organic shrinkage inhibitor may be 2000 μmol / g or more, and is preferably 3000 μmol / g or more. The upper limit of the sulfur element content of the first organic shrinkage inhibitor is not particularly limited. From the viewpoint of further enhancing the effect of reducing the amount of overcharge electricity, the sulfur element content of the organic shrinkage inhibitor is preferably 9000 μmol / g or less, and more preferably 8000 μmol / g or less.
[0122] The sulfur element content of the first organic shrink inhibitor may be, for example, 2000 μmol / g or more (or 3000 μmol / g or more) and 9000 μmol / g or less, or 2000 μmol / g or more (or 3000 μmol / g or more) and 8000 μmol / g or less.
[0123] The first organic shrinkage inhibitor includes a condensate including a unit of an aromatic compound having a sulfur-containing group, and the condensate may include at least a unit of a bisarene compound (such as a bisphenol compound) as the unit of the aromatic compound.
[0124] The weight average molecular weight (Mw) of the first organic shrink-proofing agent is preferably equal to or greater than 7000. The Mw of the first organic shrink-proofing agent is, for example, equal to or less than 100,000, and may be equal to or less than 20,000.
[0125] The negative electrode material may contain, for example, an organic shrink-proofing agent (second organic shrink-proofing agent) having a sulfur element content of less than 2000 μmol / g. The second organic shrink-proofing agent may be, among the above organic shrink-proofing agents, a lignin compound, a synthetic organic shrink-proofing agent (particularly, a lignin compound), or the like. The sulfur element content of the second organic shrink-proofing agent is preferably 1000 μmol / g or less, and may be 800 μmol / g or less. The lower limit of the sulfur element content in the second organic shrink-proofing agent is not particularly limited, and is, for example, 400 μmol / g or more.
[0126] The Mw of the second organic shrink-proofing agent is, for example, less than 7000. The Mw of the second organic shrink-proofing agent is, for example, 3000 or more.
[0127] The negative electrode material may contain a second organic shrink-proofing agent in addition to the first organic shrink-proofing agent. When the first organic shrink-proofing agent and the second organic shrink-proofing agent are used in combination, the mass ratio thereof can be selected arbitrarily.
[0128] The content of the organic shrinkage inhibitor contained in the negative electrode material is, for example, 0.005% by mass or more, and may be 0.01% by mass or more. When the content of the organic shrinkage inhibitor is in such a range, a high discharge capacity can be ensured. The content of the organic shrinkage inhibitor is, for example, 1.0% by mass or less, and may be 0.5% by mass or less. From the viewpoint of further enhancing the effect of suppressing the decrease in charge acceptance, the content of the organic shrinkage inhibitor is preferably 0.3% by mass or less, more preferably 0.25% by mass or less, and may be 0.2% by mass or less.
[0129] The content of the organic shrinkage preventer in the negative electrode material may be 0.005% by mass or more (or 0.01% by mass or more) and 1.0% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) and 0.5% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) and 0.3% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) and 0.25% by mass or less, or 0.005% by mass or more (or 0.01% by mass or more) and 0.2% by mass or less.
[0130] (carbonaceous material) Examples of the carbonaceous material contained in the negative electrode material include carbon black, graphite, hard carbon, and soft carbon. Examples of carbon black include acetylene black, furnace black, and lamp black. Furnace black also includes Ketjen Black (trade name).
[0131] In this specification, among the carbonaceous materials, -1 More than 1350cm -1 Peaks appearing in the following range (D band) and 1550 cm -1 More than 1600cm -1 Intensity ratio I to the peak (G band) appearing in the following range D / I G A carbonaceous material having a σ of 0 or more and 0.9 or less is called graphite. Graphite may be either artificial graphite or natural graphite.
[0132] The negative electrode material may contain one type of carbonaceous material or may contain two or more types of carbonaceous materials.
[0133] The content of the carbonaceous material in the negative electrode material is, for example, 0.05 mass% or more, and may be 0.10 mass% or more.The content of the carbonaceous material is, for example, 5 mass% or less, and may be 3 mass% or less.
[0134] The content of the carbonaceous material in the negative electrode material may be 0.05% by mass to 5% by mass, 0.05% by mass to 3% by mass, 0.10% by mass to 5% by mass, or 0.10% by mass to 3% by mass.
[0135] (Barium Sulfate) The content of barium sulfate in the negative electrode material is, for example, 0.05% by mass or more, and may be 0.10% by mass or more. The content of barium sulfate in the negative electrode material is, for example, 3% by mass or less, and may be 2% by mass or less.
[0136] The content of barium sulfate in the negative electrode material may be from 0.05 to 3% by mass, from 0.05 to 2% by mass, from 0.10 to 3% by mass, or from 0.10 to 2% by mass.
[0137] (Analysis of negative electrode materials or components) The method of analyzing the negative electrode material or its constituents is described below. Prior to measurement or analysis, a fully charged lead-acid battery is disassembled to obtain a negative plate to be analyzed. The obtained negative plate is washed with water to remove sulfuric acid from the negative plate. The washing is performed by pressing a pH test paper against the washed surface of the negative plate until it is confirmed that the color of the test paper does not change. However, the washing time is within 2 hours. The washed negative plate is dried at 60±5°C for about 6 hours in a reduced pressure environment. If the negative plate contains an adhesive material after drying, the adhesive material is removed by peeling. Next, the negative electrode material is separated from the negative plate to obtain a sample (hereinafter referred to as sample A). Sample A is crushed as necessary and subjected to analysis.
[0138] (1) Oxy C 2-4 Analysis of the first additive having a repeating alkylene unit structure Oxy C 2-4 The first additive having a repeating structure of an alkylene unit (specifically, a polymer compound and an oxy C 2-4 The analysis of surfactants having a repeating alkylene unit structure is carried out as follows.
[0139] (1-1) Qualitative analysis (a) OxyC 2-4 Analysis of alkylene units A ground sample A is used. 150.0±0.1 mL of chloroform is added to 100.0±0.1 g of sample A, and the mixture is stirred at 20±5° C. for 16 hours to extract the first additive. The solid content is then removed by filtration. The first additive is identified by obtaining information from at least one of infrared spectroscopy, ultraviolet-visible absorption spectroscopy, NMR spectroscopy, LC / MS, and pyrolysis GC / MS for the chloroform solution in which the first additive obtained by extraction is dissolved or the first additive obtained by drying the chloroform solution.
[0140] From the chloroform solution in which the first additive is dissolved obtained by extraction, chloroform is distilled off under reduced pressure to recover the chloroform-soluble matter. The chloroform-soluble matter is dissolved in deuterated chloroform and then subjected to the following conditions: 1 1H-NMR spectrum is measured. 1 From the H-NMR spectrum, a peak with a chemical shift in the range of 3.2 ppm to 3.8 ppm is confirmed. Also, from the peak in this range, oxy C 2-4 Identify the type of alkylene unit.
[0141] Apparatus: AL400 nuclear magnetic resonance spectrometer manufactured by JEOL Ltd. Observation frequency: 395.88MHz Pulse width: 6.30μs Pulse repetition time: 74.1411 seconds Accumulation count: 32 Measurement temperature: room temperature (20~35℃) Standard: 7.24 ppm Sample tube diameter: 5mm
[0142] (b) Analysis of hydrophobic groups in esterified products When the first additive is an ester of a hydroxy compound, a predetermined amount of the first additive obtained by drying the chloroform solution in which the first additive obtained by extraction is dissolved in (a) is collected, and an aqueous potassium hydroxide solution is added. This causes the ester to be saponified, producing a fatty acid potassium salt and a hydroxy compound. The aqueous potassium solution is added until the saponification is complete. The fatty acid potassium salt is converted to a fatty acid methyl ester by adding and mixing a solution of methanol and boron trifluoride to the resulting mixture. The resulting mixture is analyzed by pyrolysis GC-MS under the following conditions to identify the hydrophobic group contained in the ester. Analytical equipment: Shimadzu Corporation, high-performance general-purpose gas chromatogram GC-2014 Column: DEGS (diethylene glycol succinate) 2.1m Oven temperature: 180~120℃ Inlet temperature: 240℃ Detector temperature: 240℃ Carrier gas: He (flow rate: 50 mL / min) Injection volume: 1μL~2μL
[0143] (c) Analysis of hydrophobic groups in etherified products When the first additive is an etherified product of a hydroxy compound, in the above (a), a predetermined amount of the first additive obtained by drying the chloroform solution in which the first additive obtained by extraction is dissolved is collected, and hydrogen iodide is added thereto. This converts the organic group of the ether portion of the first additive (the above-mentioned R 3 ) corresponding to the iodide (R 3 I) is generated and oxy C 2-4 Diiodo C corresponding to the alkylene unit 2-4 Alkanes are produced. The hydrogen iodide is converted to etherified iodide and diiodo C. 2-4 Add a sufficient amount of ether to complete the conversion to an alkane. The resulting mixture is analyzed by pyrolysis GC-MS under the same conditions as in (b) above to identify the hydrophobic group contained in the etherified product.
[0144] (1-2) Quantitative analysis The appropriate amount of the chloroform soluble matter was measured with an accuracy of ±0.0001 g. r (g) Dissolve in deuterated chloroform together with tetrachloroethane (TCE), 1 Measure the H-NMR spectrum. The integral value (S a ) and the integral value of the peak due to TCE (S r ) and calculate the oxy-C in the negative electrode material from the following formula: 2-4 The content C by mass of the first additive having a repeating structure of an alkylene unit n Calculate the ppm.
[0145] C n =S a / S r ×N r / N a ×M a / M r ×m r / m×1000000 (In the formula, M a The molecular weight of the structure that shows a peak in the chemical shift range of 3.2 to 3.8 ppm (more specifically, oxy C 2-4 (the molecular weight of the repeating structure of alkylene units) and N a is the number of hydrogen atoms attached to the carbon atoms in the main chain of the repeating unit. r、 M r are the number of hydrogen atoms contained in the molecule of the reference material, the molecular weight of the reference material, and m (g) is the mass of the negative electrode material used for extraction.) In addition, the standard substance in this analysis is TCE, so N r =2, M r = 168. Also, m = 100.
[0146] For example, if the first additive is polypropylene glycol, M a is 58, and N a is 3. If the first additive is polyethylene glycol, M a is 44, and N a is 4. In the case of copolymers, Na and M. a are the N of each monomer unit, a Value and M a The value is calculated by averaging the molar ratio (mol %) of each monomer unit contained in the repeating structure.
[0147] In addition, in the quantitative analysis, 1 The integral value of the peak in the H-NMR spectrum is determined using data processing software “ALICE” manufactured by JEOL Ltd.
[0148] (1-3) Measurement of Mn of the first additive Using the above chloroform solubles, GPC measurement of the first additive is performed using the following apparatus under the following conditions. A calibration curve (calibration curve) is separately created from a plot of Mn of the standard substance versus elution time. Based on this calibration curve and the GPC measurement results of the first additive, the Mn of the first additive is calculated. However, esterified products or etherified products may be in a decomposed state in the chloroform solubles.
[0149] Analysis system: 20A system (Shimadzu Corporation) Column: Two GPC KF-805L (Shodex) columns connected in series Column temperature: 30℃±1℃ Mobile phase: Tetrahydrofuran Flow rate: 1mL / min. Concentration: 0.20% by mass Injection volume: 10μL Standard substance: polyethylene glycol (Mn=2,000,000, 200,000, 20,000, 2,000, 200) Detector: Differential refractive index detector (Shodex RI-201H)
[0150] (2) Analysis of surfactants Oxy C 2-4 Analysis of surfactants that do not have a repeating alkylene unit structure is carried out as follows.
[0151] (2-1) Qualitative analysis Crushed sample A is used. Approximately 1 g of sample A is collected and accurately weighed, and 5 mL of chloroform is added to prepare a mixture. The mixture is stirred for 5.5 hours at 20±5°C while applying ultrasonic waves to extract the cationic surfactant. The filtrate is then collected by filtration, and the filtered solid matter and the container are washed with chloroform to collect the washing liquid. The filtrate and washing liquid are mixed and concentrated using nitrogen gas.
[0152] The surfactant is identified by obtaining information from at least one of infrared spectroscopy, ultraviolet-visible absorption spectroscopy, NMR spectroscopy, liquid chromatography / mass spectrometry (LC / MS), and pyrolysis gas chromatography / mass spectrometry (GC / MS) for the resulting concentrate. Note that, since the counter anion of a cationic surfactant may be ion-exchanged in sulfuric acid, the structure other than the counter anion is identified.
[0153] (2-2) Quantitative analysis The concentrate obtained in the same manner as in (2-1) above is diluted with chloroform until the volume of the solution becomes 10 mL. In this way, a sample for analysis (sample B) is prepared.
[0154] The content of the surfactant in the negative electrode material is quantified by LC / MS analysis using the SRM (selected reaction monitoring) method using sample B. More specifically, the LC / MS spectrum of sample B is measured, and the concentration of the surfactant in sample B is determined by the calibration curve method from the peak intensity of a specific peak characteristic of the surfactant. The content of the surfactant in the negative electrode material is then determined from the determined concentration and the mass of sample A taken during the preparation of sample B. A calibration curve showing the relationship between the peak intensity of a specific peak and the concentration of the surfactant in the analytical material is created in advance using a surfactant that is separately prepared by qualitative analysis. For example, when the surfactant is octyltrimethylammonium chloride, a characteristic peak is detected at m / z=207.78 in the LC / MS spectrum. The LC / MS analysis is performed under the following conditions.
[0155] LC / MS equipment: LC section (Agilent Technologies, 1200 Series), MS section (Agilent Technologies, 6140) Column: Imtakt Unison UK-C18 UP (inner diameter 2 mm, length 10 cm) Column temperature: 50℃±1℃ Mobile phase: A mixture of the first and second solutions is used, and the mixing ratio of the first and second solutions is gradually changed from 20:80 (volume ratio) to 0:100 (volume ratio) over 3 minutes, and only the second solution is used from 3 minutes to 10 minutes later. First solution=aqueous solution containing 10 mmol / L ammonium formate and 10 mmol / L formic acid Second solution = methanol solution containing 10 mmol / L ammonium formate and 10 mmol / L formic acid Flow rate: 0.4mL / min Injection volume of sample B: 1 μL Detector: MS (ESI positive) Measurement mode: SCAN (mass measurement range: m / z = 100 to 1000)
[0156] (3) Analysis of organic shrinkage inhibitors (3-1) Qualitative analysis of organic shrinkage inhibitors in negative electrode materials The crushed sample A is immersed in a 1 mol / L aqueous solution of sodium hydroxide to extract the organic shrink-preventing agent. Next, the first organic shrink-preventing agent and the second organic shrink-preventing agent are separated from the extract as necessary. For each of the separated products containing each organic shrink-preventing agent, insoluble components are removed by filtration, and the resulting solution is desalted, concentrated, and dried. Desalting is performed using a desalting column, or by passing the solution through an ion exchange membrane, or by placing the solution in a dialysis tube and immersing it in distilled water. This is dried to obtain a powder sample of the organic shrink-preventing agent (hereinafter referred to as sample C).
[0157] The type of organic shrinkage inhibitor is identified by combining information obtained from the following: an infrared spectrum measured using sample C of the organic shrinkage inhibitor obtained in this manner; an ultraviolet-visible absorption spectrum measured using an ultraviolet-visible spectrometer after diluting sample C with distilled water or the like; an NMR spectrum of a solution obtained by dissolving sample C in a specified solvent such as heavy water; or information obtained from pyrolysis GC / MS, which can provide information on the individual compounds that make up the substance.
[0158] The first and second organic shrink-preventing agents are separated from the extract as follows. First, the extract is measured by infrared spectroscopy, NMR, and / or GC / MS to determine whether it contains multiple organic shrink-preventing agents. Next, the extract is analyzed by GPC to measure the molecular weight distribution. If the multiple organic shrink-preventing agents can be separated by molecular weight, the organic shrink-preventing agents are separated by column chromatography based on the difference in molecular weight. If separation based on the difference in molecular weight is difficult, one of the organic shrink-preventing agents is separated by precipitation separation using the difference in solubility that differs depending on the type and / or amount of functional groups that the organic shrink-preventing agents have. Specifically, the extract is dissolved in an aqueous NaOH solution, and an aqueous sulfuric acid solution is dropped into the mixture to adjust the pH of the mixture, thereby flocculating and separating one of the organic shrink-preventing agents. The separated product is dissolved again in an aqueous NaOH solution, and the insoluble components are removed by filtration as described above from the mixture obtained. The remaining solution after separating one of the organic shrink-preventing agents is concentrated. The resulting concentrate contains the other organic shrinkage inhibitor, and the insoluble components are removed from the concentrate by filtration as described above.
[0159] (3-2) Quantitative determination of organic shrinkage inhibitor content in negative electrode material As in the above (3-1), a solution is obtained by removing insoluble components from each of the separated products containing the organic shrinkage inhibitor by filtration. The ultraviolet-visible absorption spectrum of each of the obtained solutions is measured. The content of each organic shrinkage inhibitor in the negative electrode material is determined using the intensity of the peak characteristic of each organic shrinkage inhibitor and a calibration curve prepared in advance.
[0160] In addition, when a lead-acid battery with an unknown content of organic shrink-proofing agent is obtained and the content of the organic shrink-proofing agent is measured, the structural formula of the organic shrink-proofing agent cannot be precisely specified, so the same organic shrink-proofing agent cannot be used for the calibration curve. In this case, a calibration curve is created using the organic shrink-proofing agent extracted from the negative electrode of the battery and a separately available organic polymer that shows similar shapes in the ultraviolet-visible absorption spectrum, infrared spectroscopy spectrum, and NMR spectrum, and the content of the organic shrink-proofing agent is measured using the ultraviolet-visible absorption spectrum.
[0161] (3-3) Sulfur content in organic shrinkage inhibitors As in (3-1) above, after obtaining sample C of the organic shrink-proofing agent, the sulfur element in 0.1 g of the organic shrink-proofing agent is converted to sulfuric acid by the oxygen combustion flask method. At this time, sample C is burned in a flask containing an adsorption solution to obtain an eluate in which sulfate ions are dissolved in the adsorption solution. Next, the sulfur element content (c1) in 0.1 g of the organic shrink-proofing agent is obtained by titrating the eluate with barium perchlorate using thorin as an indicator. Next, c1 is multiplied by 10 to calculate the sulfur element content (μmol / g) in the organic shrink-proofing agent per 1 g.
[0162] (3-4) Mw measurement of organic shrinkage regulators As in (3-1) above, after obtaining sample C of the organic shrink-preventing agent, the GPC measurement of the organic shrink-preventing agent is carried out using the following apparatus under the following conditions. Separately, a calibration curve (calibration curve) is created from a plot of the Mw of the standard substance versus elution time. Based on this calibration curve and the GPC measurement results of the organic shrink-preventing agent, the Mw of the organic shrink-preventing agent is calculated.
[0163] GPC equipment: Build-up GPC system SD-8022 / DP-8020 / AS-8020 / CO-8020 / UV-8020 (Tosoh Corporation) Column: TSKgel G4000SWXL, G2000SWXL (7.8 mm I.D. x 30 cm) (Tosoh Corporation) Detector: UV detector, λ=210nm Eluent: A mixture of 1 mol / L NaCl aqueous solution: acetonitrile (volume ratio = 7:3) Flow rate: 1mL / min. Concentration: 10mg / mL Injection volume: 10μL Standard substance: Sodium polystyrene sulfonate (Mw=275,000, 35,000, 12,500, 7,500, 5,200, 1,680)
[0164] (4) Quantitative analysis of carbonaceous materials and barium sulfate Add 50 ml of 20% by mass nitric acid to 10 g of crushed sample A, heat for about 20 minutes, and dissolve the lead components as lead ions. Filter the resulting solution to separate solids such as carbonaceous materials and barium sulfate.
[0165] The obtained solid content is dispersed in water to obtain a dispersion, and then components other than the carbonaceous material and barium sulfate (e.g., reinforcing material) are removed from the dispersion using a sieve. Next, the dispersion is subjected to suction filtration using a membrane filter whose mass has been measured in advance, and the membrane filter together with the filtered sample is dried in a dryer at 110°C ± 5°C. The filtered sample is a mixed sample of the carbonaceous material and barium sulfate. The mass of the membrane filter is subtracted from the total mass of the dried mixed sample (hereinafter referred to as sample D) and the membrane filter to obtain the mass of sample D (M m ) is measured. Sample D is then placed in a crucible together with the membrane filter and incinerated at 1300°C or higher. The remaining residue is barium oxide. The mass of barium oxide is converted to the mass of barium sulfate to obtain the mass of barium sulfate (M B ) is calculated. Mass M m From mass M B The mass of the carbonaceous material is calculated by subtracting the above.
[0166] (others) The negative electrode plate can be formed by applying or filling a negative electrode paste onto a negative electrode current collector, aging and drying to prepare an unformed negative electrode plate, and then chemically forming the unformed negative electrode plate. The negative electrode paste is prepared, for example, by adding water and sulfuric acid (or an aqueous sulfuric acid solution) to lead powder, an organic shrinkage inhibitor, a first additive, and, if necessary, at least one selected from the group consisting of a carbonaceous material and other additives, and kneading the mixture. When aging, it is preferable to age the unformed negative electrode plate at a temperature higher than room temperature and at a high humidity.
[0167] The formation can be carried out by immersing the plate group including the unformed negative plate in an electrolyte containing sulfuric acid in a lead-acid battery container and charging the plate group. However, the formation may be carried out before assembling the lead-acid battery or the plate group. The formation produces spongy lead.
[0168] (Positive plate) The positive electrode plate of the lead-acid battery can be classified into a paste type, a clad type, and the like. Either a paste type or a clad type positive electrode plate may be used. The paste type positive electrode plate includes a positive electrode current collector and a positive electrode material. The configuration of the clad type positive electrode plate is as described above.
[0169] The positive electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the positive electrode current collector because it is easy to support the positive electrode material.
[0170] As the lead alloy used for the positive electrode current collector, in terms of corrosion resistance and mechanical strength, Pb-Sb alloy, Pb-Ca alloy, Pb-Ca-Sn alloy are preferable. The positive electrode current collector may have a surface layer. The surface layer and the inner layer of the positive electrode current collector may have different compositions. The surface layer may be formed on a part of the positive electrode current collector. The surface layer may be formed only on the lattice part, the edge part, or the frame part of the positive electrode current collector.
[0171] The positive electrode material contained in the positive electrode plate contains a positive electrode active material (lead dioxide or lead sulfate) that develops capacity through an oxidation-reduction reaction. The positive electrode material may contain other additives as necessary.
[0172] Unformed paste-type positive plates are obtained by filling a positive current collector with a positive paste, aging it, and drying it. The positive paste is prepared by kneading lead powder, additives, water, and sulfuric acid. Unformed clad-type positive plates are formed by filling a porous tube with lead powder or lead powder in a slurry form, into which a core metal (spine) connected by a current collector is inserted, and connecting multiple tubes with a spine protector. Then, these unformed positive plates are formed to obtain positive plates.
[0173] The formation can be carried out by immersing an electrode plate group including unformed positive plates in an electrolyte solution containing sulfuric acid in a battery container of a lead-acid battery and charging the electrode plate group in this state. However, the formation may also be carried out before assembling the lead-acid battery or the electrode plate group.
[0174] (Separator) A separator may be disposed between the negative electrode plate and the positive electrode plate, and may be made of at least one material selected from a nonwoven fabric and a microporous membrane.
[0175] A nonwoven fabric is a mat in which fibers are intertwined without being woven, and is mainly composed of fibers. For example, 60% or more by mass of the nonwoven fabric is made of fibers. As the fibers, glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (polyethylene terephthalate fibers, etc.), pulp fibers, etc.) can be used. Among them, glass fibers are preferable. The nonwoven fabric may contain components other than fibers (for example, acid-resistant inorganic powder, polymers as binders).
[0176] On the other hand, a microporous membrane is a porous sheet mainly composed of components other than fiber components, and can be obtained, for example, by extruding a composition containing a pore-forming agent into a sheet, and then removing the pore-forming agent to form pores. The microporous membrane is preferably made of an acid-resistant material, and a microporous membrane mainly composed of a polymer component is preferred. The polymer component is preferably polyolefin (polyethylene, polypropylene, etc.). The pore-forming agent can be at least one selected from the group consisting of polymer powder and oil.
[0177] The separator may be, for example, composed of only a nonwoven fabric or only a microporous membrane. Furthermore, the separator may be, as necessary, a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same materials, or a laminate of different or the same materials with recesses and projections interlocked.
[0178] The separator may be in a sheet shape or may be formed in a bag shape. A sheet-shaped separator may be sandwiched between the positive electrode plate and the negative electrode plate. Also, the electrode plate may be sandwiched between a folded sheet-shaped separator. In this case, the positive electrode plate sandwiched between the folded sheet-shaped separator and the negative electrode plate sandwiched between the folded sheet-shaped separator may be stacked, or one of the positive electrode plate and the negative electrode plate may be sandwiched between the folded sheet-shaped separator and stacked with the other electrode plate. Also, the sheet-shaped separator may be folded into a bellows shape, and the positive electrode plate and the negative electrode plate may be sandwiched between the bellows-shaped separator so that the separator is interposed between them. When a separator folded like an accordion is used, the separator may be arranged so that the folded portion is along the horizontal direction of the lead-acid battery (for example, so that the folded portion is parallel to the horizontal direction) or along the vertical direction (for example, so that the folded portion is parallel to the vertical direction). In a separator folded like an accordion, recesses are formed alternately on both main surfaces of the separator. Since the upper portions of the positive and negative plates usually have lugs, when the separator is arranged so that the folded portion is along the horizontal direction of the lead-acid battery, the positive and negative plates are arranged only in the recesses on one main surface side of the separator (that is, a double separator is interposed between the adjacent positive and negative plates). When the separator is arranged so that the folded portion is aligned with the vertical direction of the lead-acid battery, the positive electrode plate can be accommodated in the recess on one main surface side, and the negative electrode plate can be accommodated in the recess on the other main surface side (that is, a single layer of separator can be interposed between adjacent positive and negative electrode plates.) When a pouch-shaped separator is used, the pouch-shaped separator may accommodate either the positive or negative electrode plate.
[0179] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid, and may be gelled as necessary. The electrolyte contains metal ions. The metal ions contain at least one first component selected from the group consisting of lithium ions, sodium ions, and aluminum ions. When the electrolyte contains the first component, it is possible to obtain an effect of reducing the overcharge electricity quantity, an effect of improving the charge acceptance, and an effect of improving the PSOC life performance by direct or indirect interaction with the first additive contained in the negative electrode material.
[0180] From the viewpoint of ensuring higher charge acceptance and PSOC life performance, the electrolyte may contain at least one of lithium ions and sodium ions, and aluminum ions. In this case, the overcharge quantity of electricity can be further reduced. Among them, when the first component contains at least lithium ions and aluminum ions, it is preferable because the charge acceptance can be further improved.
[0181] The concentration of each of the first components in the electrolyte may be 0.35 mol / L or less. From the viewpoint of easily ensuring higher charge acceptance and PSOC life performance, the concentration of each of the first components is preferably 0.3 mol / L or less or 0.25 mol / L or less, and may be 0.2 mol / L or less. The concentration of each of the first components is determined, for example, so that the total concentration of the first components is 0.02 mol / L or more. The concentration of each of the first components is, for example, 0.01 mol / L or more, and may be 0.02 mol / L or more.
[0182] The concentration of each of the first components in the electrolyte may be 0.01 mol / L or more (or 0.02 mol / L or more) and 0.35 mol / L or less, 0.01 mol / L or more (or 0.02 mol / L or more) and 0.3 mol / L or less, 0.01 mol / L or more (or 0.02 mol / L or more) and 0.25 mol / L or less, or 0.01 mol / L or more (or 0.02 mol / L or more) and 0.2 mol / L or less.
[0183] The total concentration of the first components in the electrolyte is 0.02 mol / L or more. By setting the total concentration of the first components in this range, excellent charge acceptance can be ensured. The upper limit of the total concentration of the first components can be determined according to the concentration of each of the first components. From the viewpoint of easily ensuring higher charge acceptance and PSOC life performance, the total concentration of the first components is preferably 0.7 mol / L or less, and may be 0.5 mol / L or less or 0.4 mol / L or less.
[0184] Even if the components of a lead-acid battery other than the electrolyte, such as the negative plate, the positive plate, and the separator, contain the same metal component (metal compound, etc.) as the first component, the content of the metal component in the components is small and the effect on the concentration of the first component in the electrolyte is small. Specifically, even if the components other than the electrolyte contain the same metal component as the first component (for example, sodium lignin sulfonate in the negative electrode material, sodium salt as a surfactant), when an electrolyte to which the first component or a compound that generates the first component is not added is used, the total concentration of the first component in the electrolyte is less than 0.02 mol / L (usually less than 0.01 mol / L).
[0185] The electrolytic solution may contain at least one selected from the group consisting of cations (e.g., metal cations) other than the first component, and anions (e.g., anions other than sulfate anions (e.g., phosphate ions)). The metal cations other than the first component may be referred to as the second component. Examples of the second component include magnesium ions and potassium ions.
[0186] The total concentration of the second component in the electrolytic solution may be, for example, 0.01 mol / L or less. It is also preferable that the electrolytic solution does not contain the second component. In addition, when the electrolytic solution does not contain the second component, the second component in the electrolytic solution is below the detection limit.
[0187] The electrolyte may include the first additive described above.
[0188] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. is, for example, 1.20 or more, and may be 1.25 or more. The specific gravity of the electrolyte at 20° C. is 1.35 or less, and preferably 1.32 or less.
[0189] The specific gravity of the electrolyte at 20° C. may be 1.20 or more and 1.35 or less, 1.20 or more and 1.32 or less, 1.25 or more and 1.35 or less, or 1.25 or more and 1.32 or less.
[0190] The respective concentrations of the first and second components in the electrolyte are determined by inductively coupled plasma (ICP) emission spectroscopy of the electrolyte taken out of a fully charged lead-acid battery. More specifically, an ICP emission spectrometer is used to identify the type of metal ion in the electrolyte and measure the emission intensity of the metal ion. The concentration of the metal ion in the electrolyte is determined from the measured emission luminosity and a calibration curve prepared in advance. The ICPS-8000 manufactured by Shimadzu Corporation is used as the ICP emission spectrometer.
[0191] (others) The lead-acid battery can be obtained by a manufacturing method including a step of housing a plate group and an electrolyte in a cell chamber of a battery case. Each cell of the lead-acid battery includes a plate group and an electrolyte housed in each cell chamber. The plate group is assembled by stacking a positive electrode plate, a negative electrode plate, and a separator such that the separator is interposed between the positive electrode plate and the negative electrode plate prior to housing in the cell chamber. The positive electrode plate, the negative electrode plate, the electrolyte, and the separator are each prepared prior to assembling the plate group. The manufacturing method of the lead-acid battery may include a step of chemically forming at least one of the positive electrode plate and the negative electrode plate, as necessary, after the step of housing the plate group and the electrolyte in the cell chamber.
[0192] Each plate in the plate group may be one or more. When the plate group includes two or more negative plates, if at least one negative plate satisfies the condition that the negative electrode material contains the first additive, the charge acceptance of the negative plate is improved, and the effect of reducing the amount of overcharge electricity and the effect of improving PSOC life performance are obtained according to the number of such negative plates. From the viewpoint of ensuring higher charge acceptance and PSOC life performance while keeping the amount of overcharge electricity low, it is preferable that 50% or more (more preferably 80% or more or 90% or more) of the number of negative plates included in the plate group are negative plates that satisfy the above condition. The ratio of the negative plates that satisfy the above condition among the negative plates included in the plate group is 100% or less. All of the negative plates included in the plate group may be negative plates that satisfy the above condition.
[0193] When the lead-acid battery has two or more cells, it is sufficient that the plate groups of at least some of the cells have negative plates that satisfy the above conditions. From the viewpoint of further suppressing the decrease in charge acceptance and ensuring a high effect of reducing the overcharged amount of electricity, it is preferable that 50% or more (more preferably 80% or more or 90% or more) of the number of cells included in the lead-acid battery have plate groups including negative plates that satisfy the above conditions. The ratio of cells included in the lead-acid battery that have plate groups including negative plates that satisfy the above conditions is 100% or less. It is preferable that all of the plate groups included in the lead-acid battery have negative plates that satisfy the above conditions.
[0194] FIG. 1 shows an external appearance of an example of a lead-acid battery according to one embodiment of the present invention. The lead-acid battery 1 includes a battery case 12 that contains a plate group 11 and an electrolyte (not shown). The battery case 12 is divided into a plurality of cell chambers 14 by partition walls 13. Each cell chamber 14 contains one plate group 11. The opening of the battery case 12 is closed by a lid 15 that has a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When refilling with water, the vent plug 18 is removed and refilling liquid is added. The vent plug 18 may have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.
[0195] Each electrode plate group 11 is formed by stacking a plurality of negative electrode plates 2 and positive electrode plates 3 with a separator 4 interposed therebetween. Here, a pouch-shaped separator 4 that accommodates the negative electrode plates 2 is shown, but the shape of the separator is not particularly limited. In a cell chamber 14 located at one end of the battery case 12, a negative electrode shelf portion 6 that connects a plurality of negative electrode plates 2 in parallel is connected to a through connector 8, and a positive electrode shelf portion 5 that connects a plurality of positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 outside the lid 15. In a cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode shelf portion 6, and a through connector 8 is connected to the positive electrode shelf portion 5. The negative electrode column 9 is connected to a negative electrode terminal 16 outside the lid 15. Each through connector 8 passes through a through hole provided in the partition wall 13 to connect the electrode plate groups 11 of adjacent cell chambers 14 in series.
[0196] The positive electrode shelf 5 is formed by welding the lugs provided on the upper part of each positive electrode plate 3 together by a cast-on-strap method or a burning method. The negative electrode shelf 6 is also formed by welding the lugs provided on the upper part of each negative electrode plate 2 together in the same manner as the positive electrode shelf 5.
[0197] The lid 15 of the lead-acid battery has a single structure (single lid), but is not limited to the illustrated example. The lid 15 may have a double structure including, for example, an inner lid and an outer lid (or a top lid). The lid having a double structure may have a reflux structure between the inner lid and the outer lid for returning the electrolyte to the inside of the battery (inside the inner lid) from a reflux port provided in the inner lid.
[0198] In this specification, the overcharge quantity of electricity, PSOC life performance, and charge acceptance are evaluated according to the following procedures: The rated voltage of the test battery used in the evaluation is 2 V / cell, and the rated 5-hour rate capacity is 32 Ah.
[0199] (a) Overcharged electricity Using the above test battery, the overcharged electrical quantity is evaluated under the following conditions. In order to create more overcharge conditions than the normal 4-10 minute test specified in JIS D5301:2019, a 1 minute discharge-10 minute charge test (1-10 minute test) is performed at 75°C ± 3°C (high temperature light load test). In the high temperature light load test, charge and discharge are repeated 1220 cycles. The overcharge quantity of electricity (charge quantity of electricity - discharge quantity of electricity) in each cycle up to the 1220th cycle is totaled and averaged to determine the overcharge quantity of electricity (Ah) per cycle. Discharge: 25A, 1 minute Charging: 2.47V / cell, 25A, 10 minutes Water tank temperature: 75℃±3℃
[0200] (b) PSOC life performance The lead-acid battery is charged and discharged in the pattern shown in Table 1. The number of cycles until the terminal voltage reaches 1.2 V per cell is used as an index of PSOC life performance.
[0201] [Table 1]
[0202] (c) Charge acceptance Using a fully charged test battery, measure the amount of electricity at 10 seconds. Specifically, the test battery is discharged at 6.4A for 30 minutes and left for 16 hours. After that, the upper limit of the current is set to 200A and the test battery is charged at 2.42V / cell. Determine The battery is charged at a voltage and the accumulated quantity of electricity for 10 seconds (the quantity of electricity at the 10th second) is measured. Both operations are carried out in a water tank at 25°C ± 2°C. The accumulated quantity of electricity for 10 seconds is used as an index for evaluating the charge acceptance.
[0203] A lead-acid battery according to one aspect of the present invention will be described below.
[0204] (1) A lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate comprises a negative electrode material, The negative electrode material is a surfactant and oxy C 2-4 The composition includes at least one additive (first additive) selected from the group consisting of polymer compounds having a repeating structure of alkylene units, and an organic shrink-proofing agent, The electrolyte contains metal ions, the metal ion includes at least one component (first component) selected from the group consisting of a lithium ion, a sodium ion, and an aluminum ion; The total concentration of the components in the electrolyte is 0.02 mol / L or more; A lead-acid battery, wherein the concentration of each of the components in the electrolyte is 0.35 mol / L or less.
[0205] (2) In the above (1), the concentration of each of the first components may be 0.3 mol / L or less, 0.25 mol / L or less, or 0.2 mol / L or less.
[0206] (3) In the above (1) or (2), the concentration of each of the first components may be 0.01 mol / L or more, or 0.02 mol / L or more.
[0207] (4) In any one of the above (1) to (3), the total concentration of the first component may be 0.7 mol / L or less, 0.5 mol / L or less, or 0.4 mol / L or less.
[0208] (5) In any one of the above (1) to (4), the first component may contain at least one of lithium ions and sodium ions, and aluminum ions.
[0209] (6) In any one of the above (1) to (5), the first component may contain at least lithium ions and aluminum ions.
[0210] (7) In any one of the above (1) to (6), the first additive is the polymer compound (oxy C 2-4 (including nonionic surfactants having a repeating alkylene unit structure), The polymer compound may include a compound having an Mn of 5 million or less, 1 million or less, 100,000 or less, 50,000 or less, 20,000 or less, 10,000 or less, 9,000 or less, or 8,000 or less.
[0211] (8) In the above (7), the Mn of the compound may be 300 or more, 400 or more, 500 or more, 1000 or more, or 1500 or more.
[0212] (9) In any one of the above (1) to (8), the first additive is oxy C 2-4 The hydroxy compound includes at least one selected from the group consisting of a hydroxy compound having a repeating structure of an alkylene unit, an etherified product of the hydroxy compound, and an esterified product of the hydroxy compound, The hydroxy compound is polyC 2-4 Alkylene glycol, oxy C 2-4 Copolymers containing repeating alkylene units, and polyol polyC 2-4 It may be at least one selected from the group consisting of alkylene oxide adducts.
[0213] (10) In any one of the above (1) to (9), the first additive may contain a compound (polymer compound) having a repeating structure of oxypropylene units.
[0214] (11) In the above (10), the number average molecular weight of the compound (polymer compound) may be 1,000 or more and 10,000 or less, or 1,500 or more and 10,000 or less.
[0215] (12) In the above (10) or (11), the polymer compound is polypropylene glycol, polyoxypropylene-polyoxyethylene copolymer (polyoxypropylene-polyoxyethylene block copolymer, etc.), polypropylene glycol alkyl ether (the above R 2 alkyl ethers (methyl ether, ethyl ether, butyl ether, etc.) in which R is an alkyl having 10 or less carbon atoms (or 8 or less or 6 or less), etc.), polyoxyethylene-polyoxypropylene alkyl ethers (the above R 2 alkyl ethers (butyl ether, hydroxyhexyl ether, etc.) in which R is an alkyl having 10 or less carbon atoms (or 8 or less or 6 or less), polypropylene glycol carboxylates (the above R 3 may contain at least one selected from the group consisting of polypropylene glycol carboxylates (such as polypropylene glycol acetate) in which the alkyl group has 10 or less carbon atoms (or 8 or less, or 6 or less), and polypropylene oxide adducts of triol or higher polyols (such as polypropylene oxide adducts of glycerin).
[0216] (13) In any one of the above (10) to (12), the proportion of the oxypropylene units in the polymer compound may be 5 mol % or more, 10 mol % or more, or 20 mol % or more.
[0217] (14) In any one of the above (10) to (13), the proportion of the oxypropylene unit in the polymer compound may be 100 mol % or less.
[0218] (15) In any one of the above (10) to (14), the compound (polymer compound) may not contain a repeating structure of an oxyethylene unit.
[0219] (16) In any one of the above (1) to (15), it is preferable that the first additive (particularly, the surfactant) does not contain elemental sulfur.
[0220] (17) In any one of the above (1) to (16), the surfactant may include a cationic surfactant.
[0221] (18) In the above (17), the cationic surfactant may contain a quaternary ammonium salt.
[0222] (19) In any one of the above (1) to (18), the negative electrode material contains a carbonaceous material, The first additive has at least one hydrophobic group and one hydrophilic group, At least one of the hydrophobic groups may be a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms.
[0223] (20) In the above (19), the long-chain aliphatic hydrocarbon group may have 30 or less, 26 or less, 24 or less, or 22 or less carbon atoms.
[0224] (21) In any one of the above (1) to (18), the negative electrode material may further contain a carbonaceous material.
[0225] (22) In any one of the above (19) to (21), the content of the carbonaceous material in the negative electrode material may be 0.05 mass % or more, or 0.10 mass % or more.
[0226] (23) In any one of the above (19) to (22), the content of the carbonaceous material in the negative electrode material may be 5 mass % or less, or 3 mass % or less.
[0227] (24) In any one of the above (1) to (23), the content of the first additive in the negative electrode material may be, by mass, 8 ppm or more, 10 ppm or more, 50 ppm or more, 100 ppm or more, 300 ppm or more, or 400 ppm or more.
[0228] (25) In any one of the above (1) to (24), the content of the first additive in the negative electrode material may be, by mass, 10,000 ppm or less, 6,000 ppm or less, 5,000 ppm or less, 1,000 ppm or less, or 700 ppm or less.
[0229] (26) In any one of the above (1) to (25), the content of the organic shrink-preventing agent in the negative electrode material may be 0.005% by mass or more, or 0.01% by mass or more.
[0230] (27) In any one of the above (1) to (26), the content of the organic shrinkage preventer in the negative electrode material may be 1.0 mass % or less, 0.5 mass % or less, 0.3 mass % or less, 0.25 mass % or less, or 0.2 mass % or less.
[0231] (28) In any one of the above (1) to (27), the organic shrink-proofer (or the negative electrode material) may contain a first organic shrink-proofer having a sulfur element content of 2000 μmol / g or more or 3000 μmol / g or more.
[0232] (29) In the above (28), the sulfur element content of the first organic shrink-proofing agent may be 9000 μmol / g or less, or 8000 μmol / g or less.
[0233] (30) In the above (28) or (29), the first organic shrink-preventing agent may have an Mw of 7,000 or more.
[0234] (31) In any one of the above (28) to (30), the first organic shrink-preventing agent may have an Mw of 100,000 or less, or 20,000 or less.
[0235] (32) In any one of the above (1) to (31), the organic shrink-proofing agent (or the first organic shrink-proofing agent) may contain a condensation product of a bisarene compound.
[0236] (33) In any one of the above (1) to (32), the negative electrode material may further contain barium sulfate.
[0237] (34) In the above (33), the content of the barium sulfate in the negative electrode material may be 0.05% by mass or more, or 0.10% by mass or more.
[0238] (35) In the above (34), the content of the barium sulfate in the negative electrode material may be 3 mass % or less, or 2 mass % or less.
[0239] (36) In any one of the above (1) to (35), the specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. may be 1.20 or more or 1.25 or more.
[0240] (37) In any one of the above (1) to (36), the specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. may be 1.35 or less or 1.32 or less.
[0241] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0242] Lead-acid batteries E1 to E40, C1 to C4, and R1 to R4 (1) Preparation of lead-acid batteries (a) Preparation of the negative electrode plate The raw material lead powder, barium sulfate, carbon black, the first additive shown in Tables 2 to 4, and the organic shrinkage inhibitor shown in Tables 2 to 4 are mixed with an appropriate amount of sulfuric acid aqueous solution to obtain a negative electrode paste. At this time, the components are mixed so that the contents of the first additive and the organic shrinkage inhibitor in the negative electrode material, which are all obtained by the above-mentioned procedures, are the values shown in Tables 2 to 4, the barium sulfate content is 0.4 mass% and the carbon black content is 0.2 mass%. The negative electrode paste is filled into the mesh part of an expanded lattice made of a Pb-Ca-Sn alloy, and aged and dried to obtain an unformed negative electrode plate.
[0243] As the organic shrink inhibitors shown in the table, the following components are used. (e1) Lignin: Sodium lignosulfonate (sulfur element content 600 μmol / g, Mw 5500) (e2) Bisphenol condensate: Condensation product of a bisphenol compound with a sulfonic acid group introduced with formaldehyde (sulfur element content 4000 μmol / g, Mw 8000)
[0244] (b) Preparation of the positive electrode plate The raw lead powder is mixed with an aqueous sulfuric acid solution to obtain a positive electrode paste, which is then filled into the mesh of an expanded lattice made of a Pb-Ca-Sn alloy, aged and dried to obtain an unformed positive electrode plate.
[0245] (c) Preparation of lead-acid battery The lead-acid battery has a rated voltage of 2V / cell and a rated 5-hour rate capacity of 32Ah. The plate group of the test battery is composed of seven positive plates and seven negative plates. The negative plates are housed in a pouch-shaped separator made of a polyethylene microporous film and are alternately stacked with the positive plates to form a plate group. The plate group is housed in a polypropylene battery case together with an electrolyte, and chemical formation is performed in the battery case to prepare a liquid-type lead-acid battery. The specific gravity of the electrolyte in a fully charged lead-acid battery at 20°C is 1.28. As the electrolyte, an aqueous sulfuric acid solution containing a metal sulfate corresponding to the first component shown in Tables 2 to 4 is used. The amount of metal sulfate added is adjusted so that the concentration of each of the first components obtained by the above-mentioned procedure is the value shown in Tables 2 to 4.
[0246] However, when the Na ion concentration in the table is <0.01 mol / L, the Na ion comes from the sodium lignosulfonate used in the negative electrode material, and when it is <0.002 mol / L, the Na ion comes from the first additive. In these cases, the electrolyte is prepared without adding sodium sulfate.
[0247] (2) Evaluation (a) Overcharged electricity Using the above-mentioned lead-acid batteries, the overcharged amount of electricity (Ah) per cycle is calculated using the procedure described above. The overcharged amount of electricity of each lead-acid battery is evaluated as a ratio (%) of the overcharged amount of electricity (Ah) per cycle of the lead-acid battery C1, which is set to 100.
[0248] (b) PSOC life performance The above-mentioned lead-acid batteries are used to evaluate the PSOC life performance according to the procedure described above. The PSOC life performance of each lead-acid battery is expressed as a percentage (%) with the result of the lead-acid battery C1 taken as 100.
[0249] (c) Charge acceptance The charge acceptance of the fully charged lead-acid batteries is evaluated according to the procedure described above. The charge acceptance of each lead-acid battery is evaluated as a ratio (%) of the integrated amount of electricity of the lead-acid battery C1, which is set to 100.
[0250] The results are shown in Tables 2 to 4. The Mn of polypropylene glycol and polyethylene glycol is the Mn determined by the procedure described above. In Table 2, the Mn of the esterified product is the Mn of the esterified product used in preparing the negative electrode material. Lead-acid batteries E1 to E40 are examples. Lead-acid batteries C1 to C4 are comparative examples. Lead-acid batteries R1 to R4 are reference examples.
[0251] [Table 2]
[0252] As shown in Table 2, even when an electrolyte containing the first component at a total concentration of 0.02 mol / L or more is used, when it is combined with a negative electrode plate containing an organic shrinkage inhibitor but not a first additive, the charge acceptance is improved, but the overcharge charge cannot be reduced (comparison between C1 and C2). Even when a lead-acid battery is equipped with a negative electrode material containing an organic shrinkage inhibitor and a first additive, if the electrolyte does not contain the first component at a total concentration of 0.02 mol / L or more, the overcharge charge can be reduced, but the charge acceptance is reduced (comparison between C1 and R1). In contrast to these results, when a negative electrode plate containing a negative electrode material containing an organic shrinkage inhibitor and a first additive is combined with an electrolyte containing the first component at a total concentration of 0.02 mol / L or more, the charge acceptance can be greatly improved while reducing the overcharge charge (comparison between C1, C2, and R1 and E1). In addition, the PSOC life can be greatly improved in E1.
[0253] From C1, C2, and R1, when the electrolyte contains the first component at a total concentration of 0.02 mol / L or more, the charge acceptance is improved by 12%, the overcharge charge remains unchanged, and the PSOC life performance is improved by 54%. Also, when the negative electrode material contains the first additive in addition to the organic shrinkage inhibitor, the charge acceptance is reduced by 35%, the overcharge charge is reduced by 25%, and the PSOC life performance is improved by 10%. From these results, when an electrolyte containing the first component at a total concentration of 0.02 mol / L or more is combined with a negative plate having a negative electrode material containing an organic shrinkage inhibitor and a first additive, the charge acceptance is expected to be 77% (=100+12-35), the overcharge charge is 75% (=100+0-25), and the PSOC life performance is 164% (=100+54+10). However, in reality, E1 has a charge acceptance of 121%, an overcharge charge of 65%, and a PSOC life performance of 184%. These results for E1 are far better than those expected for C1, C2, and R1, and show that a synergistic effect is obtained by combining the electrolyte and the negative plate.
[0254] The relationship between C3, C4, and R2 and E2 is the same as above, and in the case of a synthetic organic shrinkage inhibitor, a synergistic effect can be obtained in all of improving the charge acceptance and PSOC life performance, and reducing the amount of overcharge electricity.
[0255] Furthermore, not only when polypropylene glycol is used as the first additive, but also when polyethylene glycol, an ester, or a surfactant is used, the same or similar effects as those of E2 are obtained (E5 to E11).
[0256] From the viewpoint of ensuring higher charge acceptance, PSOC life performance, and a smaller overcharge charge, it is preferable that the first additive does not contain sulfur element, and it is preferable to use a cationic surfactant (comparison between E8 to E9 and E1 to E7). From the same viewpoint, it is preferable to use a first additive containing a compound having a repeating structure of oxypropylene units, and it is more preferable that such a compound does not contain a repeating structure of oxyethylene units (comparison between E5 and E2 to E4).
[0257] From the viewpoint of easily ensuring higher charge acceptance and PSOC life performance, it is preferable that at least one of the hydrophobic groups of the surfactant is a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms (comparison between E6 and E7).
[0258] [Table 3]
[0259] As shown in Table 3, excellent effects can be obtained even when the content of the first additive in the negative electrode material is changed. From the viewpoint of obtaining a higher effect, the content of the first additive is preferably 10 ppm or more (or 50 ppm or more) and 10,000 ppm or less, and may be 100 ppm or more and 8,000 ppm or less.
[0260] [Table 4]
[0261] As shown in Table 4, when the total concentration of the first components in the electrolyte is less than 0.02 mol / L, the effect of improving the charge acceptance is hardly obtained (R3 and R4). In contrast, when the total concentration of the first components in the electrolyte is 0.02 mol / L or more, the charge acceptance and PSOC life performance are significantly improved (comparison of R3 and R4 with E2 and E15 to E40). From the viewpoint of further facilitating the reduction of the overcharged electric quantity, the concentration of each of the first components in the electrolyte is 0.35 mol / L or less, preferably 0.3 mol / L or less, and more preferably 0.25 mol / L or less or 0.2 mol / L or less.
[0262] From the viewpoint of ensuring higher charge acceptance and PSOC life performance, it is preferable that the first component contains at least one of Li ions and Na ions, and Al ions (compare E15 to E18 with E2 and E20 to E34, and compare E36 to E38 with E39 and E40). In this case, the overcharge quantity of electricity can be further suppressed.
[0263] From the viewpoint of ensuring higher charge acceptance, it is preferable that the first component contains at least Li ions and Al ions (comparison of E15, E17, E18, E20, and E2 with E36 to E40). [Industrial Applicability]
[0264] The lead-acid battery according to one aspect of the present invention is suitable for use in an idle-stop vehicle as an IS lead-acid battery that is charged and discharged under PSOC conditions. The lead-acid battery can also be suitably used as a starting power source for vehicles (such as automobiles and motorcycles) and industrial power storage devices (such as power sources for electric vehicles (such as forklifts)). Note that these are merely examples, and the uses of the lead-acid battery are not limited to these. [Explanation of symbols]
[0265] 1:Lead acid battery 2: Negative plate 3: Positive plate 4: Separator 5: Positive electrode shelf 6: Negative electrode shelf 7: Positive pole 8: Through connector 9: Negative pole 11: Plate group 12:Battery container 13: Bulkhead 14: Cell Room 15: Lid 16: Negative terminal 17: Positive terminal 18: Liquid outlet plug
Claims
1. A lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate comprises a negative electrode material, The negative electrode material is a surfactant and oxyC 2-4 The composition includes at least one additive selected from the group consisting of polymer compounds having a repeating structure of alkylene units, and an organic shrink-preventing agent, The content of the additive in the negative electrode material is 0.001% by mass or more and 0.5% by mass or less, The electrolyte contains metal ions, The metal ions include at least one component selected from the group consisting of lithium ions, sodium ions, and aluminum ions; The total concentration of the components in the electrolyte is 0.02 mol / L or more, A lead-acid battery, wherein the concentration of each of the components in the electrolyte is 0.35 mol / L or less.
2. 2. The lead-acid battery according to claim 1, wherein the concentration of each of the components is from 0.01 mol / L to 0.25 mol / L.
3. The lead-acid battery according to claim 1 or 2, wherein the components include at least one of lithium ions and sodium ions, and aluminum ions.
4. The lead acid battery according to any one of claims 1 to 3, wherein the components include at least lithium ions and aluminum ions.
5. The additive does not contain elemental sulfur, The additive includes a compound having a repeating structure of oxypropylene units, The number average molecular weight of the compound is 1,000 or more and 10,000 or less, The lead acid battery according to any one of claims 1 to 4, wherein the compound does not contain a repeating structure of an oxyethylene unit.
6. The lead acid battery according to any one of claims 1 to 5, wherein the surfactant includes a cationic surfactant.
7. 7. The lead acid battery of claim 6, wherein the cationic surfactant comprises a quaternary ammonium salt.
8. The negative electrode material includes a carbonaceous material, The additive has at least one hydrophobic group and one hydrophilic group, The lead acid battery according to any one of claims 1 to 7, wherein at least one of the hydrophobic groups is a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms.
9. The lead acid battery according to any one of claims 1 to 8, wherein the organic shrinkage inhibitor comprises a condensate of a bisarene compound.
10. The lead acid battery according to any one of claims 1 to 9, wherein the total concentration of the components is 0.7 mol / L or less.
11. The lead acid battery according to any one of claims 1 to 10, wherein the total concentration of the components is 0.5 mol / L or less.
Citation Information
Patent Citations
High-molecular nano polymer electrolyte for lead-acid battery and its compounding method
CN100439438C
Lead-acid battery
JP1985182662A
Lead-acid battery
JP1997147869A
Lead acid storage battery
JP2006004636A
Electrolytic solution for lead storage battery, anode for lead storage battery, lead storage battery equipped with electrolytic solution and / or anode, and additive for lead acid battery
JP2008152973A